Electrophotographic Imaging System
The electrophotographic image forming system enhances abrasion and filming resistance by using a photoreceptor with polycarbonate resin, inorganic fine particles, and dual particle size lubricants, along with a fog toner supply mechanism, addressing image defects in low-temperature, low-humidity environments.
Patent Information
- Application Number
- JP2021097405
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-10
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-06-10
AI Technical Summary
Existing electrophotographic image forming systems face issues with both abrasion resistance and filming resistance, particularly in low-temperature, low-humidity environments, leading to image defects such as white spots due to deposits from developer materials.
The system incorporates a photoreceptor with a photosensitive layer containing polycarbonate resin, inorganic fine particles, and a charge transport material, along with toner particles having a dual particle size distribution of lubricants and a fog toner supply mechanism to enhance abrasion and filming resistance.
The solution effectively improves both abrasion and filming resistance, reducing surface wear and deposits, thereby minimizing image defects and ensuring high-quality image output.
Smart Images

Figure 0007613280000013 
Figure 0007613280000014 
Figure 0007613280000015
Abstract
Description
[Technical field]
[0001] The present invention relates to electrophotographic imaging systems. More particularly, the present invention relates to an electrophotographic image forming system that satisfies both the wear resistance and filming resistance of a photoreceptor. [Background technology]
[0002] 2. Description of the Related Art In photoreceptors used in electrophotographic image forming systems, a technique has been disclosed in which inorganic fine particles are incorporated into the outermost surface layer in order to improve abrasion resistance (see Patent Documents 1 and 2).
[0003] However, these techniques can improve abrasion resistance, but have a problem of insufficient filming resistance. Particularly in low temperature and low humidity environments and environments accompanied by close-proximity discharge due to contact charging members, developer-derived deposits tend to form on the photoconductor, and the deposits cause image defects such as white spots on the formed image. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-316036 A [Patent Document 2] JP 2006-301247 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in consideration of the above problems and circumstances, and an object of the present invention is to provide an electrophotographic image forming system which achieves both high wear resistance and high filming resistance for a photoconductor. [Means for solving the problem]
[0006] In order to solve the above problems, the present inventors have investigated the causes of the above problems and have found that an electrophotographic image forming system can be provided which achieves both abrasion resistance and filming resistance of a photosensitive member by incorporating a polycarbonate resin having a relatively rigid skeleton, inorganic fine particles and a charge transport material into the outermost layer of a photosensitive layer, using a lubricant having a peak on the large particle size side (hereinafter also referred to as "lubricant on the large particle size side") and a lubricant having a peak on the small particle size side (hereinafter also referred to as "lubricant on the small particle size side") together as external additives to toner particles, and further providing a fogging toner supply mechanism which supplies the toner particles to a cleaning means by applying the toner particles to non-image areas on a photosensitive member, thereby arriving at the present invention. That is, the above-mentioned problems of the present invention are solved by the following means.
[0007] 1. An electrophotographic imaging system for forming an image with toner particles, comprising: The image forming apparatus includes a photoconductor, a charging unit, an exposure unit, a developing unit, a transfer unit, and a cleaning unit, The photoreceptor is configured by laminating a photosensitive layer on a conductive support, the photosensitive layer has at least a charge generating layer and a charge transport layer, the outermost layer of the photosensitive layer contains a polycarbonate having a partial structure represented by the following general formula (1), inorganic fine particles, and a charge transport material, the toner particles contain toner base particles and an external additive, The external additive is at least a lubricant, the volumetric average particle size distribution of the lubricant has two peaks, one on the small particle side and the other on the large particle side, the volumetric average particle size of the lubricant having the peak on the small particle side is 3.0 μm or less, and the volumetric average particle size of the lubricant having the peak on the large particle side is larger than the volumetric average particle size of the toner base particles, A fog toner supply mechanism is provided for supplying the toner particles to the cleaning means by applying the toner particles to a non-image area on the photoreceptor. 23. An electrophotographic imaging system comprising: [ka] (In the formula, R1 and R2 each independently represent a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or Phenyl group At least one of R1 and R2 represents Phenyl group Also, R3 to R 10 each independently represents a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms.
[0008] 2. The electrophotographic imaging system of claim 1, wherein said photosensitive layer has a protective layer as said outermost layer.
[0009] 3. The outermost layer of the photosensitive layer further contains a polycarbonate having a partial structure represented by the following general formula (2): 3. The electrophotographic imaging system according to claim 1 or 2. [ka]
[0010] 4. The number average primary particle size of the inorganic fine particles is within the range of 5 to 100 nm. 4. The electrophotographic imaging system according to any one of claims 1 to 3.
[0011] 5. The inorganic fine particles are hydrophobic silica. 5. The electrophotographic imaging system according to any one of claims 1 to 4.
[0012] 6. The volume-based average particle size of the lubricant having a peak on the small particle size side is within the range of 1.0 to 3.0 μm, and the volume-based average particle size of the lubricant having a peak on the large particle size side is within the range of 8.0 to 15.0 μm. 6. The electrophotographic imaging system according to any one of claims 1 to 5,
[0013] 7. The lubricant is at least one of zinc stearate particles, lithium stearate particles, and magnesium stearate particles. 7. The electrophotographic imaging system according to any one of claims 1 to 6.
[0014] 8. The fog toner supply mechanism applies the toner particles to the non-image area on the photoconductor by making the fog margin of the non-image area on the photoconductor different from the fog margin of the image area on the photoconductor. 8. The electrophotographic imaging system according to any one of claims 1 to 7.
[0015] 9. The transfer means applies a transfer bias having the same polarity as the toner particles to the non-image area on the photoreceptor. 9. The electrophotographic imaging system according to any one of claims 1 to 8.
[0016] 10. The cleaning means is provided with a cleaning blade that is pressed against the surface of the photoreceptor so that the edge angle of the tip edge is within the range of 90 to 130 degrees. 10. The electrophotographic imaging system according to any one of claims 1 to 9.
[0017] 11. The charging means is of a contact type. 11. The electrophotographic imaging system of any one of claims 1 to 10. Effect of the Invention
[0018] According to the above-mentioned means of the present invention, it is possible to provide an electrophotographic image forming system in which the photoconductor has both high wear resistance and high filming resistance.
[0019] Although the mechanism by which the effects of the present invention are manifested or the mechanism by which the effects of the present invention are acted upon has not been clearly understood, it is speculated as follows.
[0020] As described above, by incorporating inorganic fine particles in the outermost layer of the photoreceptor, the abrasion resistance is improved. On the other hand, if inorganic fine particles are contained, the inorganic fine particles may aggregate due to interaction with the binder resin during the heating and drying process of the coating liquid in the manufacturing process of the photoreceptor, and the phenomenon of coarse particles being precipitated on the surface of the photoreceptor may occur. Generally, the toner particles originating from the developer remaining on the surface of the photoreceptor are scraped off and collected by a cleaning blade, but if coarse particles are present on the surface of the photoreceptor, the toner particles are not scraped off and tend to pass through the cleaning blade while remaining attached to the surface of the photoreceptor. The discharge energy during the next charging process after passing through the cleaning blade generates discharge decomposition products such as the binder resin of the toner particles, and these discharge-produced decomposition products serve as a medium to cause adhesion between the coarse particles on the surface of the photoreceptor and the toner external additive. This phenomenon is repeated, and visible-sized deposits are formed on the surface of the photoreceptor, resulting in white spots on the image. This phenomenon is called the filming phenomenon.
[0021] In the heat drying process after application, the inorganic fine particles dispersed in advance are thought to flow in the softened binder resin medium. If the binder resin skeleton has a flexible chemical structure, the flowability of the inorganic fine particles in the heat drying process increases, which leads to promotion of re-aggregation of the inorganic fine particles. Here, it can be assumed that if the polycarbonate resin having a relatively rigid skeleton according to the present invention is used as the binder resin, the re-aggregation of the inorganic fine particles is restricted, and as a result, the generation of coarse particles on the surface of the photoreceptor can be suppressed. This improves filming resistance.
[0022] Furthermore, by using a lubricant having a large particle diameter and a lubricant having a small particle diameter as external additives to the toner particles, the abrasion resistance and filming resistance of the photoreceptor can be further improved.
[0023] The lubricant on the large particle size side is easily separated from the toner base particles, so it is easy to adhere to the low coverage image area on the photoreceptor. On the other hand, the lubricant on the small particle size side is not easily separated from the toner base particles, so it is easy to adhere to the high coverage image area where the toner base particles move. In this way, by using the lubricant on the large particle size side and the lubricant on the small particle size side in combination, the lubricant can be attached to the photoreceptor surface regardless of the coverage, and is efficiently supplied to the cleaning process. The lubricant supplied to the cleaning process contributes to preventing the photoreceptor from wearing and preventing the toner particles from slipping through by reducing the friction force between the photoreceptor surface and the cleaning blade. This improves the wear resistance and filming resistance of the photoreceptor.
[0024] The fog toner supply mechanism, which supplies toner particles to the cleaning means by applying the toner particles to the non-image areas on the photoreceptor, is a mechanism for further suppressing non-uniformity in the distribution of the lubricant.
[0025] The lubricant on the large particle size side is easily separated from the toner base particles, so that when the developer is transported in the axial direction of the photoconductor, a large amount of the lubricant is supplied upstream in the transport direction. This causes a gradient in the amount of lubricant adhering in the axial direction of the photoconductor, and the photoconductor surface is less likely to be scraped in the area with a large amount of lubricant, resulting in a gradient in the amount of wear on the photoconductor surface in the axial direction. In addition, when the lubricant on the large particle size side and the lubricant on the small particle size side are used in combination, the overall amount of lubricant adhering increases, and the effect of the lubricant memory also increases accordingly, and the unevenness of the distribution tends to increase. The lubricant memory refers to the uneven distribution of the lubricant that occurs according to the coverage difference when there is a difference in image coverage in the axial direction of the photoconductor. In this way, when the lubricant on the large particle size side and the lubricant on the small particle size side are used in combination, the axial gradient in the amount of lubricant adhering and the effect of the lubricant memory increase, and the amount of lubricant adhering tends to become uneven.
[0026] Here, by deliberately forcibly generating fogging toner (toner that adheres to non-image areas) and supplying it to the cleaning means, the toner particles scrape off the lubricant in areas with a high amount of lubricant adhesion, making the amount of lubricant adhesion uniform.
[0027] It is presumed that the above-mentioned mechanism of occurrence or action enables the electrophotographic image forming system of the present invention to achieve both abrasion resistance and filming resistance of the photoreceptor. [Brief description of the drawings]
[0028] [Figure 1] FIG. 1 is a diagram for explaining an example of a particle size distribution of a lubricant having peaks on the small particle side and the large particle side. [Diagram 2] FIG. 1 is a diagram for explaining the cumulative frequency and content ratio of a particle size distribution of a lubricant having peaks on the small particle side and the large particle side. [Diagram 3] Cross-sectional schematic diagram of the basic layer structure of a photoreceptor [Figure 4] Hydrophobicity distribution curve of inorganic fine particles [Diagram 5] FIG. 1 is a cross-sectional view illustrating an example of a configuration of an image forming apparatus. [Figure 6] FIG. 1 is an explanatory cross-sectional view showing an example of a configuration of a main part of an image forming apparatus. [Figure 7] FIG. 1 is a schematic diagram showing an example of the configuration of a charging unit; [Figure 8] A schematic diagram showing the relationship between the cleaning blade and the photoconductor from the side DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The electrophotographic image forming system of the present invention is an electrophotographic image forming system that forms an image using toner particles, and includes a photoconductor, a charging unit, an exposure unit, a developing unit, a transfer unit, and a cleaning unit. The photoconductor is configured by laminating a photosensitive layer on a conductive support, the photosensitive layer has at least a charge generating layer and a charge transport layer, the outermost layer of the photosensitive layer contains a polycarbonate having a partial structure represented by the above general formula (1), inorganic fine particles, and a charge transport material, and the toner particles are composed of toner base particles and an outer The toner cleaning device further comprises a fogging toner supply mechanism that supplies the toner particles to the cleaning means by applying the toner particles to non-image areas on the photoconductor. The fogging toner supply mechanism is characterized in that the volume-based particle size distribution of the lubricant has two peaks, one on the small particle side and the other on the large particle side, the volume-based average particle size of the lubricant having the peak on the small particle side is 3.0 μm or less, and the volume-based average particle size of the lubricant having the peak on the large particle side is larger than the volume-based average particle size of the toner base particles. This feature is a technical feature common to or corresponding to the following embodiments.
[0030] In an embodiment of the present invention, from the viewpoint of suppressing variation in thickness in the outermost layer of the photoreceptor, the photosensitive layer preferably has a protective layer as the outermost layer.
[0031] From the viewpoint of suppressing micro-crystallization of the resin in a low-temperature environment, it is preferable that the outermost layer of the photosensitive layer further contains a polycarbonate having a partial structure represented by the above general formula (2).
[0032] From the viewpoint of suppressing the formation of coarse particles that are aggregates of inorganic fine particles, the number average primary particle size of the inorganic fine particles is preferably within the range of 5 to 100 nm.
[0033] From the viewpoint of easy dispersion in the binder resin, the inorganic fine particles are preferably hydrophobic silica.
[0034] From the viewpoint of being able to supply the lubricant efficiently and uniformly in the axial direction to the cleaning means, it is preferable that the volume-based average particle size of the lubricant having a peak on the small particle size side is within the range of 1.0 to 3.0 μm, and the volume-based average particle size of the lubricant having a peak on the large particle size side is within the range of 8.0 to 15.0 μm.
[0035] From the viewpoint of electrical polarity, the lubricant is preferably at least one of zinc stearate particles, lithium stearate particles, and magnesium stearate particles.
[0036] From the viewpoint of efficiently supplying toner particles, it is preferable that the fog toner supply mechanism applies toner particles to the non-image areas on the photoreceptor by making the fog margin of the non-image areas on the photoreceptor different from the fog margin of the image areas on the photoreceptor.
[0037] From the viewpoint that the toner particles applied to the non-image areas on the photosensitive body by the fog toner supply mechanism are less likely to transfer to the transfer body and can be efficiently supplied to the cleaning means, it is preferable that the transfer means applies a transfer bias of the same polarity as the toner particles to the non-image areas on the photosensitive body.
[0038] From the viewpoint of reducing stick-slip vibration of the cleaning blade, improving the slip-through of toner particles, and improving cleaning performance, it is preferable that the cleaning means comprises a cleaning blade that is pressed against the surface of the photoreceptor so that the edge angle of the tip ridgeline is within the range of 90 to 130°.
[0039] From the viewpoint of generating less harmful ozone gas in the charging process, it is preferable that the charging means be of the contact type.
[0040] The present invention, its components, and embodiments for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values before and after the symbol "to" are included as the lower limit and upper limit.
[0041] <1 Overview of Electrophotographic Image Forming System> The electrophotographic image forming system of the present invention (hereinafter, also simply referred to as "image forming system") is an electrophotographic image forming system that forms an image using toner particles, and includes a photoconductor, a charging unit, an exposure unit, a developing unit, a transfer unit, and a cleaning unit. The photoconductor is configured by laminating a photosensitive layer on a conductive support, the photosensitive layer has at least a charge generating layer and a charge transport layer, the outermost layer of the photosensitive layer contains a polycarbonate having a partial structure represented by the following general formula (1), inorganic fine particles, and a charge transport material, and the toner particles are the lubricant has a volumetric average particle size distribution having two peaks, one on the small particle side and one on the large particle side, the volumetric average particle size of the lubricant having the peak on the small particle side being 3.0 μm or less, and the volumetric average particle size of the lubricant having the peak on the large particle side being larger than the volumetric average particle size of the toner base particles; and the toner cleaning device is provided with a fogging toner supply mechanism that supplies the toner particles to the cleaning means by applying the toner particles to non-image areas on the photoconductor.
[0042] In the image forming system of the present invention, the device section is particularly referred to as an "image forming apparatus", and the image forming system of the present invention forms an image by using the image forming apparatus and the toner particles of the present invention.
[0043] The toner particles and each configuration of the image forming apparatus will be described below.
[0044] <2 Toner particles> The toner particles according to the present invention contain toner base particles and an external additive, the external additive being at least a lubricant, the volume-based particle size distribution of the lubricant having two peaks, one on the small particle size side and one on the large particle size side, the volume-based average particle size of the lubricant having the peak on the small particle size side being 3.0 μm or less, and the volume-based average particle size of the lubricant having the peak on the large particle size side being larger than the volume-based average particle size of the toner base particles.
[0045] In the present invention, the term "toner base particles" refers to a particle that constitutes the base of "toner particles." The "toner base particles" contain at least a binder resin and a colorant, and may contain other components such as a release agent (wax) and a charge control agent as necessary. The "toner base particles" are called "toner particles" when an external additive is added. And, "toner" refers to an aggregate of "toner particles."
[0046] <2.1 Lubricants> The toner particles according to the present invention contain a lubricant as an external additive.
[0047] The lubricant according to the present invention is characterized in that its volume-based particle size distribution has two peaks, one on the small particle side and one on the large particle side, the volume-based average particle size of the lubricant having the peak on the small particle side is 3.0 μm or less, and the volume-based average particle size of the lubricant having the peak on the large particle side is larger than the volume-based average particle size of the toner base particles.
[0048] The lubricant supplied onto the photoreceptor is spread onto the photoreceptor by the cleaning blade. The lubricant spread onto the photoreceptor reduces friction between the cleaning blade and the surface of the photoreceptor, thereby improving the cleaning performance of the residual toner on the photoreceptor (toner that has not been transferred to the transfer medium and remains on the photoreceptor).
[0049] As the lubricant used in the present invention, a fatty acid metal salt is preferable from the viewpoint of spreadability on the photoreceptor, and furthermore, it is preferable that the Mohs hardness is 2 or less. As such a fatty acid metal salt, a salt of a metal selected from zinc, calcium, magnesium, aluminum, and lithium is preferable. Among these, fatty acid zinc, fatty acid lithium, or fatty acid magnesium is particularly preferable. In addition, as the fatty acid of the fatty acid metal salt, a higher fatty acid having 12 to 22 carbon atoms is preferable. When a fatty acid having 12 or more carbon atoms is used, the generation of free fatty acid can be suppressed, and when the carbon number of the fatty acid is 22 or less, the melting point of the fatty acid metal salt is not too high, and good fixability can be obtained. As the fatty acid, stearic acid is particularly preferable, and as the fatty acid metal salt particles used in the present invention, zinc stearate particles, lithium stearate particles, or magnesium stearate particles are preferable from the viewpoint of electric polarity.
[0050] In the present invention, in order to make the particle size distribution of the lubricant contained in the toner have two peaks, one on the small particle side and the other on the large particle side, it is preferable to use two lubricants with different average particle sizes. Here, the two lubricants may differ only in average particle size, or two lubricants made of different materials may be used in combination.
[0051] The volumetric particle size distribution of the lubricant has two peaks, one on the small particle side and one on the large particle side, in order to reduce the difference in the amount of application between the image area and the non-image area, and the volumetric average particle size of the lubricant having the peak on the small particle side is 3.0 μm or less, and the volumetric average particle size of the lubricant having the peak on the large particle side is larger than the volumetric average particle size of the toner base particles.
[0052] When the volume-based average particle diameter of the lubricant having a peak on the small particle diameter side is 3.0 μm or less, it adheres to the toner particles and exhibits the function of adhering to the high coverage image area on the photoreceptor. Furthermore, it is preferable that the volume-based average particle diameter of the lubricant having a peak on the small particle diameter side is within the range of 1.0 to 3.0 μm. By being 1.0 μm or more, the amount of the lubricant adhered is not too small, and by being 3.0 μm or less, it is difficult to separate from the toner base particles, and it is easy to adhere to the low coverage image area.
[0053] The volume-based average particle diameter of the lubricant having a peak on the large particle diameter side is larger than the volume-based average particle diameter of the toner base particles. If the volume-based average particle diameter is larger than that of the toner base particles, the lubricant will not adhere to the toner particles and will function to be developed in non-image areas independently of the toner particles. Furthermore, it is preferable that the volume-based average particle diameter of the lubricant having a peak on the large particle diameter side is within the range of 8.0 to 15.0 μm. By being 8.0 μm or more, the lubricant will be easily separated from the toner base particles and will easily adhere to low coverage image areas, and by being 15.0 μm or less, the variation in the amount of adhesion in the axial direction can be suppressed.
[0054] The volumetric particle size of the lubricant can be measured, for example, by using a flow type particle image analyzer "FPIA-2100" (manufactured by Sysmex Corporation) after separating the toner base particles and external additives from the toner, for example, according to the following procedure.
[0055] 5 g of toner particles and 50 ml of 0.7% sodium dodecylbenzenesulfonate aqueous solution are placed in a 100 ml beaker, and the mixture is stirred at 300 rpm for 5 minutes using a magnetic stirrer "Model MS500D" (manufactured by Yamato Scientific) to disperse the toner particles.
[0056] After the dispersion, the toner dispersion is subjected to ultrasonic vibrations using an ultrasonic homogenizer "US-1200T" (manufactured by Nippon Seiki Seisakusho) at a frequency of 20 kHz, OUTPUT scale 3, and TUNING scale 6 for 10 minutes.
[0057] The toner dispersion is separated by centrifuging using a centrifuge (Model H-900, manufactured by Kokusan) under the following conditions. Rotor: PC-400 (radius 18.1 cm) Rotation speed: 1200 rpm (292 G) Time: 10 minutes
[0058] After centrifugation, 40 ml of the supernatant is collected. At this time, a pipette is used to carefully collect the supernatant so as not to include the settled toner base particles.
[0059] The volumetric particle size of the external additive contained in the collected supernatant is measured using a flow particle image analyzer "FPIA-2100" (manufactured by Sysmex Corporation), whereby the volumetric particle size distribution and the volumetric average particle size can be determined.
[0060] The measurement range is 0.6 to 400 μm. Since the external additives other than the lubricant added to the toner base particles have a size of 0.6 μm or less, by measuring at 0.6 to 400 μm, the external additives other than the lubricant are not measured, and the particle size distribution measured in this measurement range corresponds to the particle size distribution of the lubricant.
[0061] FIG. 1 is a diagram for explaining an example of a volumetric particle size distribution of a lubricant having peaks on the small particle side and the large particle side, where a is an example of a particle size distribution of a lubricant that has been added to a toner base particle as an external additive in the past. b is an example of a volumetric particle size distribution of a lubricant having two peaks on the small particle side and the large particle side according to the present invention, where P1 is the peak on the small particle side and P2 is the peak on the large particle side. D indicates the particle size of the minimum value of the particle size distribution curve. The content ratio is calculated by dividing the small particle side and the large particle side from this minimum particle size D. That is, each content ratio is a value when the volumetric particle size distribution of the lubricant shown in FIG. 1 is divided into two, the small particle side and the large particle side, at the minimum particle size D.
[0062] Fig. 2 shows the integrated frequency of the volumetric particle size distribution of the lubricant, and is a diagram for explaining the content ratio of lubricants having a peak on the small particle size side and lubricants having a peak on the large particle size side. Here, the integrated frequency value (intersection with D) at the minimum particle size D of the particle size distribution represents the content ratio of lubricants having a peak on the small particle size side.
[0063] The lubricant according to the present invention preferably has a volumetric particle size distribution with two peaks, one on the small particle side and the other on the large particle side, and the content of the lubricant with the peak on the small particle side is 50 to 70 mass % of the total lubricant. Within this range, the ratio of the lubricant supplied to the image area and the non-image area becomes almost the same, which is preferable because the lubricant can be supplied to the entire surface of the photoreceptor.
[0064] The respective content ratios are values obtained by dividing the volumetric particle size distribution of the lubricant shown in FIG. 1 into two, the small particle size side and the large particle size side, at the minimum particle size D.
[0065] The content of the lubricant in the toner is preferably 0.01 to 0.5 parts by mass per 100 parts by mass of the toner base particles, in order to obtain a sufficient lubricating effect.
[0066] <2.2 Toner base particles> Known toner base particles can be used as the toner base particles. Specifically, such toner base particles are composed of toner base particles containing at least a binder resin (hereinafter also referred to as "toner resin") and a colorant. In addition, the toner base particles can further contain other components such as a release agent and a charge control agent, if necessary.
[0067] The volume-based average particle size of the toner base particles is preferably within the range of 5.0 to 8.0 μm. When the volume-based average particle size of the toner base particles is within this range, a high-definition image can be obtained.
[0068] The average circularity (shape factor) of the toner base particles is preferably from 0.930 to 0.990, and more preferably from 0.955 to 0.980, from the viewpoint of improving flowability.
[0069] (Method of measuring average circularity and volume-based average particle size of toner base particles) The average circularity and volume-based average particle diameter of the toner base particles can be measured, for example, using a flow type particle image analyzer "FPIA-2100" (manufactured by Sysmex Corporation). Specifically, the toner is mixed with an aqueous solution containing a surfactant, and dispersed by ultrasonic dispersion treatment for 1 minute, and then photographed with "FPIA-2100" (manufactured by Sysmex Corporation) under the measurement conditions of HPF (high magnification imaging) mode at an appropriate concentration of 3,000 to 10,000 HPF detections, to measure the average circularity and volume-based average particle diameter.
[0070] Regarding the circularity, the circularity of each toner base particle is calculated by the following formula (1), and the average circularity is calculated. Here, the "circle equivalent diameter" refers to the diameter of a circle having the same area as the particle image.
[0071] Formula (1): Circularity = Perimeter of circle calculated from equivalent diameter / Perimeter of projected particle image
[0072] (Toner binder resin) As the binder resin constituting the toner, it is preferable to use a thermoplastic resin.
[0073] As such a binder resin, any resin generally used as a binder resin constituting a toner can be used without any particular limitation. Specific examples of such a binder resin include styrene-based resins, acrylic resins such as alkyl acrylates and alkyl methacrylates, styrene-acrylic copolymer resins, polyester resins, silicone resins, olefin-based resins, amide resins, and epoxy resins.
[0074] Among these, styrene resins, acrylic resins, styrene-acrylic copolymer resins, and polyester resins are preferred because they have low viscosity and high sharp melting properties. As the main resin, it is preferable to use styrene-acrylic copolymer resins in an amount of 50% or more. These resins can be used alone or in combination of two or more.
[0075] Examples of the polymerizable monomer for obtaining the binder resin include styrene-based monomers such as styrene, methylstyrene, methoxystyrene, butylstyrene, phenylstyrene, and chlorostyrene; acrylic acid ester-based monomers such as methyl acrylate, ethyl acrylate, butyl acrylate, and ethylhexyl acrylate; methacrylic acid ester-based monomers such as methyl methacrylate, ethyl methacrylate, butyl methacrylate, and ethylhexyl methacrylate; and carboxylic acid-based monomers such as acrylic acid, methacrylic acid, and fumaric acid.
[0076] These can be used alone or in combination of two or more.
[0077] From the viewpoint of low-temperature fixability, the binder resin constituting the toner preferably has a glass transition temperature (Tg) of 30 to 50° C. If the glass transition temperature is within this range, the low-temperature fixability and heat-resistant storage stability are excellent.
[0078] The glass transition temperature of the binder resin can be measured using a Diamond DSC (manufactured by PerkinElmer).
[0079] The measurement procedure involves sealing 3.0 mg of binder resin in an aluminum pan and setting it in a holder. An empty aluminum pan is used as a reference. The measurement conditions are a measurement temperature of 0 to 200°C, a heating rate of 10°C / min, a cooling rate of 10°C / min, and temperature control of heat-cool-heat (Heat-Cool-Heat), and analysis is performed based on the data from the second heating (2nd Heat).
[0080] The glass transition temperature is determined by drawing an extension of the baseline before the onset of the first endothermic peak and a tangent line showing the maximum slope between the onset of the first peak and the peak apex, and the intersection of these lines is indicated as the glass transition point.
[0081] The glass transition temperature (Tg) of the toner is measured by the same method as above, using the toner as a measurement sample.
[0082] Furthermore, the softening temperature of the binder resin is preferably 80 to 130° C., and more preferably 90 to 120° C. The softening temperature can be measured, for example, by a flow tester “CFT-500D” (manufactured by Shimadzu Corporation).
[0083] The softening temperature is measured, for example, as follows.
[0084] First, in an environment of 20±1°C temperature and 50±5% relative humidity, 1.1 g of sample was placed in a petri dish, flattened, and left for 12 hours or more. After that, it was pressed to 3820 kg / cm using a molding machine "SSP-10A" (Shimadzu Corporation). 2 The molded sample was then extruded from the cylindrical die hole (1 mm diameter x 1 mm) using a piston with a diameter of 1 cm at the end of preheating under the conditions of a load of 196 N (20 kgf), a starting temperature of 60 °C, a preheating time of 300 seconds, and a heating rate of 6 °C / min using a flow tester "CFT-500D" (Shimadzu Corporation). The offset method temperature T was measured using a melting temperature measurement method with an offset value of 5 mm. 0ffset is taken as the softening temperature of the sample.
[0085] The softening temperature of the toner is measured using the toner as a sample in the same manner as above.
[0086] (Coloring agent) As the colorant constituting the toner base particles, known inorganic or organic colorants can be used.
[0087] The amount of the colorant added is in the range of 1 to 30% by mass, preferably 2 to 20% by mass, based on the total mass of the toner.
[0088] (Release agent) The toner base particles may contain a release agent. The release agent is not particularly limited, and examples thereof include hydrocarbon waxes such as polyethylene wax, oxidized polyethylene wax, polypropylene wax, and oxidized polypropylene wax, carnauba wax, fatty acid ester wax, sazol wax, rice wax, candelilla wax, jojoba oil wax, and beeswax wax.
[0089] The content of the release agent in the toner base particles is usually 1 to 30 parts by mass, and more preferably 5 to 20 parts by mass, per 100 parts by mass of the binder resin for forming the toner base particles.
[0090] (Charge control agent) The toner base particles may contain a charge control agent, such as a metal complex of a salicylic acid derivative with zinc or aluminum (salicylic acid metal complex), a calixarene compound, an organic boron compound, or a fluorine-containing quaternary ammonium salt compound.
[0091] The content of the charge control agent in the toner base particles is usually in the range of 0.1 to 5.0 parts by mass with respect to 100 parts by mass of the binder resin.
[0092] <2.3 Manufacturing method of toner base particles> The toner particles according to the present invention are obtained by adding an external additive to a toner base particle, and methods for producing the toner base particle include a kneading and pulverization method, a suspension polymerization method, an emulsion aggregation method, a dissolution suspension method, a polyester elongation method, and a dispersion polymerization method.
[0093] Among these, it is preferable to employ the emulsion aggregation method from the viewpoints of uniformity of particle size, which is advantageous for high image quality and high stability, controllability of shape, and ease of formation of a core-shell structure.
[0094] The emulsion aggregation method is a method for producing toner base particles by mixing a dispersion of resin fine particles dispersed with a surfactant or a dispersion stabilizer with a dispersion of toner base particle constituents such as colorant fine particles as necessary, aggregating the particles to the desired toner particle size by adding an aggregating agent, and then, or simultaneously with the aggregating, fusing the resin fine particles together and controlling the shape.
[0095] Here, the resin microparticles may optionally contain internal additives such as a release agent and a charge control agent, and may also be composite particles formed of multiple layers having a composition of two or more layers made of resins with different compositions.
[0096] From the viewpoint of toner structure design, it is also preferable to add different kinds of resin particles during aggregation to form toner base particles having a core-shell structure.
[0097] The resin microparticles can be produced, for example, by emulsion polymerization, mini-emulsion polymerization, phase inversion emulsification, etc., or by a combination of several production methods. When an internal additive is to be contained in the resin microparticles, it is preferable to use the mini-emulsion polymerization method.
[0098] <2.4 External additives other than lubricants> In addition to the lubricant, it is preferable to add fine particles such as known inorganic fine particles or organic fine particles as external additives to the surface of the toner base particles in order to improve the charging performance and flowability of the toner. As the inorganic fine particles, it is preferable to use inorganic oxide fine particles such as silica, titania, or alumina, and further, it is preferable that these inorganic fine particles are hydrophobized with a silane coupling agent, a titanium coupling agent, or the like.
[0099] As the organic fine particles, polymers such as polystyrene, polymethyl methacrylate, and styrene-methyl methacrylate copolymers can be used.
[0100] The total amount of the inorganic fine particles and organic fine particles added is preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the toner base particles.
[0101] (metal oxide fine particles) In the toner particles according to the present invention, it is preferable to add metal oxide fine particles having a high abrasive effect in order to further enhance the abrasive effect on the photoreceptor surface. As the metal oxide fine particles having a high abrasive effect, silica fine particles, alumina fine particles, cerium oxide fine particles, calcium titanate fine particles, or strontium titanate fine particles having a number-average primary particle size in the range of 100 to 300 nm are preferable. Among these, calcium titanate fine particles or strontium titanate fine particles are particularly preferable. By being contained in the toner particles as an external additive, these metal oxide fine particles are deposited at the tip of the cleaning blade to exert a refreshing effect on the photoreceptor surface as an abrasive, and have the effect of suppressing the occurrence of black dot-like image defects on the photoreceptor surface by polishing the excess lubricant spread on the photoreceptor, and the effect of removing discharge products, and also have the effect of controlling the fluidity and charging performance of the toner. In addition, the content of these metal oxide fine particles having an abrasive effect is preferably within the range of 0.05 to 5 parts by mass, preferably 0.1 to 3 parts by mass, of the metal oxide fine particles relative to 100 parts by mass of the toner base particles.
[0102] From the viewpoint of heat resistance storage property and environmental stability, it is preferable that these metal oxide fine particles are surface-treated with a silane coupling agent, a titanium coupling agent, a higher fatty acid, a silicone oil or the like.
[0103] <2.5 How to add external additives> The external additive addition step is a step of preparing toner particles by adding and mixing an external additive to the dried toner base particles.
[0104] The method of adding the external additive includes a dry method in which the external additive is added in powder form to dried toner base particles, and the mixing device includes a mechanical mixer such as a Henschel mixer or a coffee mill.
[0105] In the present invention, it is preferable to add and mix the lubricant in two stages in order to control the particle size distribution of the lubricant. Specifically, it is preferable to first add and mix a lubricant having a peak on the small particle size side, and then add and mix a lubricant having a peak on the large particle size side. External additives other than the lubricant, such as metal oxide fine particles, may be added and mixed in any of the above two stages.
[0106] <2.6 Developer> The toner particles according to the present invention can be used as a magnetic or non-magnetic one-component developer in the image forming system of the present invention, but may also be mixed with carrier particles to be used as a two-component developer. When using this toner as a two-component developer, the carrier particles may be magnetic particles made of conventionally known materials such as metals such as iron, ferrite, and magnetite, and alloys of these metals with metals such as aluminum and lead, and ferrite particles are particularly preferred. In addition, the carrier particles may be resin-coated carrier particles in which the surfaces of magnetic particles are coated with a coating agent such as resin, or binder-type carrier particles in which magnetic fine powder is dispersed in a binder resin.
[0107] The coating resin constituting the resin-coated carrier particles is not particularly limited, and examples thereof include olefin resins, styrene resins, styrene-acrylic resins, acrylic resins, silicone resins, ester resins, and fluororesins. The binder resin constituting the binder-type carrier particles is not particularly limited, and known resins can be used, and examples thereof include styrene-acrylic resins, polyester resins, fluororesins, and phenol resins. Among these, resin-coated carrier particles coated with styrene-acrylic resins or acrylic resins are preferred from the viewpoints of electrostatic chargeability and durability.
[0108] The carrier particles preferably have a volume average particle size of 20 to 100 μm, more preferably 25 to 80 μm, in order to obtain a high-quality image and suppress carrier adhesion. The volume average particle size of the carrier particles can be measured typically by a laser diffraction particle size distribution measuring device "HELOS" (manufactured by Sympatec Co., Ltd.) equipped with a wet disperser.
[0109] <3 Photoreceptor> The photoreceptor according to the present invention is configured by laminating a photosensitive layer on a conductive support, the photosensitive layer having at least a charge generating layer and a charge transporting layer, and the outermost layer of the photosensitive layer contains a polycarbonate having a partial structure represented by the following general formula (1), inorganic fine particles, and a charge transporting material.
[0110] There are two types of photoreceptors: negatively charged photoreceptors and positively charged photoreceptors. A negatively charged photoreceptor has a layer structure in which at least a charge generating layer and a charge transport layer are laminated in this order on a conductive support. A positively charged photoreceptor has a layer structure in which at least a charge transport layer and a charge generating layer are laminated in this order on a conductive support. In the present invention, a negatively charged photoreceptor is preferable.
[0111] 3 is a cross-sectional schematic diagram of the basic layer structure of a photoreceptor according to the present invention. Photoreceptor 310 according to the present invention has a photosensitive layer 302 on a conductive support 301. The photosensitive layer has at least a charge generating layer 304 and a charge transport layer 305, and may have an intermediate layer 303 between the conductive support 301 and the photosensitive layer 302. In addition, a protective layer 306 may be further provided on the charge transport layer 305.
[0112] In this specification, the "outermost layer of the photosensitive layer" refers to, for example, the charge transport layer 305 when no protective layer is present (Figure 3(a)), and refers to the protective layer 306 when a protective layer is present (Figure 3(b)).
[0113] Preferred layer structures of the photoreceptor according to the present invention are given below. (1) A layer structure in which a charge generating layer, a charge transport layer, and a protective layer are laminated in this order on a conductive support. (2) A layer structure in which a layer containing a charge generating material and a charge transporting material in the same layer, and a protective layer are laminated in this order on a conductive support. (3) A layer structure in which an intermediate layer, a charge generating layer, a charge transport layer, and a protective layer are laminated in this order on a conductive support. (4) A layer structure in which an intermediate layer, a layer containing a charge generating material and a charge transporting material in the same layer, and a protective layer are laminated in this order on a conductive support.
[0114] In the present invention, the charge generation layer and the charge transport layer can be formed as a single layer containing a charge generation material and a charge transport material in the same layer. However, from the viewpoints of suppressing an increase in residual potential that occurs with repeated use and further facilitating control of various electrophotographic properties according to purpose, it is preferable to form each of them as a separate layer.
[0115] From the viewpoint of abrasion resistance, it is preferable to have a protective layer. From these viewpoints, the layer structure of (1) or (3) is preferable, and the layer structure of (3) is particularly preferable.
[0116] <3.1 Photosensitive layer> The photosensitive layer is a layer for forming an electrostatic latent image corresponding to a desired image on the surface of a photoreceptor by exposure to light. In the present invention, the photosensitive layer has at least a charge generating layer and a charge transport layer.
[0117] As described above, the charge generating layer and the charge transporting layer may be formed as a single layer, but it is preferable that the charge generating layer and the charge transporting layer have a layer structure in which their functions are separated from each other. Furthermore, it is preferable that the photosensitive layer has a protective layer.
[0118] <3.1.1 Top surface layer> The photoreceptor according to the present invention is characterized in that the outermost layer of the photosensitive layer contains a polycarbonate having a partial structure represented by the following general formula (1), inorganic fine particles, and a charge transport material. Usually, the outermost layer of the photosensitive layer is composed of a charge transport material dispersed in a binder resin, and the outermost layer contains a charge transport material, so that an electrostatic latent image can be formed on the surface of the photoreceptor. Furthermore, the outermost layer contains inorganic fine particles, so that abrasion resistance is obtained. In the present invention, the outermost layer further contains a polycarbonate having a partial structure represented by the following general formula (1) as a binder resin, so that the inorganic fine particles are less likely to aggregate, and filming resistance is obtained.
[0119] The "top surface layer" is usually also called the "surface layer" or "outermost layer" and refers to a layer disposed at the outermost side that comes into contact with the toner. The top surface layer is disposed at the top of the photosensitive layer as viewed from the conductive support side, and can also be said to be a layer that constitutes the surface of the photoreceptor. In the present invention, when the photoreceptor has a protective layer, the top surface layer refers to the protective layer, and when the photoreceptor does not have a protective layer, the top surface layer refers to a charge transport layer or a layer that contains a charge generating material and a charge transport material in the same layer.
[0120] (binder resin) The term "binder resin" refers to a resin used as a medium or matrix (parent body) for dispersing materials, and in the outermost layer of the photosensitive layer according to the present invention, refers to a resin used for dispersing inorganic fine particles and charge transport material.
[0121] The binder resin of the outermost layer may be a polycarbonate having a partial structure represented by the following general formula (1) used alone or in combination with other binder resins. The other binder resins are not particularly limited and may be known resins, such as polycarbonate resins, polyacrylate resins, polyester resins, polystyrene resins, styrene-acrylonitrile copolymers, polymethacrylic acid ester resins, and styrene-methacrylic acid ester copolymers.
[0122] Among these, polycarbonate resins are preferred from the viewpoint of compatibility with charge transport materials, and examples thereof include bisphenol Z type polycarbonate obtained by polymerizing bisphenol Z as one of the raw materials, which is a polycarbonate having a partial structure represented by the following general formula (2). By using a polycarbonate having a partial structure represented by the following general formula (1) in combination with a bisphenol Z type polycarbonate, micro-crystallization of the resin in a low-temperature environment is suppressed, and high filming resistance is obtained in a low-temperature, low-humidity environment.
[0123] (Polycarbonate) The polycarbonate used as the binder resin of the outermost layer has a partial structure represented by the following general formula (1). [ka] (In the formula, R1 and R2 each independently represent a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms, and at least one of R1 and R2 represents an aryl group. 10 each independently represents a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms.
[0124] By containing a polycarbonate having a partial structure represented by the above general formula (1), which is a relatively rigid skeleton, in the outermost layer, the inorganic fine particles described below are easily dispersed in the binder resin and are less likely to aggregate, thereby achieving resistance to filming.
[0125] Examples of the alkyl group having 1 to 6 carbon atoms represented by R1 and R2 include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a 1-methylpropyl group, a 2-methylpropyl group, a 1,1-dimethylethyl group (tert-butyl group), an n-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 3-methylbutyl group, a 1-ethylpropyl group, a 1,1-dimethylpropyl group, a 1,2-dimethylpropyl group, a 2,2-dimethylpropyl group (neopentyl group), and an n-hexyl group. , 1-methylpentyl group, 2-methylpentyl group, 3-methylpentyl group, 4-methylpentyl group, 1,1-dimethylbutyl group, 1,2-dimethylbutyl group, 1,3-dimethylbutyl group, 2,2-dimethylbutyl group, 2,3-dimethylbutyl group, 3,3-dimethylbutyl group, 1-ethylbutyl group, 2-ethylbutyl group, 1,1,2-trimethylpropyl group, 1,2,2-trimethylpropyl group, 1-ethyl-1-methylpropyl group, and 1-ethyl-2-methylpropyl group.
[0126] The aryl group having 6 to 12 carbon atoms represented by R1 and R2 is preferably a phenyl group or an alkyl group substituted with a phenyl group, more preferably a phenyl group. The number of carbon atoms in the alkyl group substituted with a phenyl group is preferably 1 to 3, more preferably 1 or 2, and even more preferably 1.
[0127] R3~R 10 Examples of the halogen atom represented by the formula (I) include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Examples of the alkyl group having 1 to 6 carbon atoms include those similar to the examples of the alkyl group having 1 to 6 carbon atoms represented by R1 and R2.
[0128] Examples of polycarbonates having a partial structure represented by general formula (1) include polycarbonates obtained by polymerizing bisphenol AP (1,1-bis(4-hydroxyphenyl)-1-phenylethane) and a compound having a substituent introduced into its benzene ring as one of the raw materials, and polycarbonates obtained by polymerizing bisphenol BP (bis(4-hydroxyphenyl)diphenylmethane) and a compound having a substituent introduced into its benzene ring as one of the raw materials. In particular, bisphenol AP-type polycarbonates obtained by polymerizing bisphenol AP as one of the raw materials have a rigid binder skeleton compared to other polycarbonates, and high filming resistance can be obtained.
[0129] The polycarbonate having a partial structure represented by the general formula (1) may be a homopolymer or a copolymer, and the copolymer may have any of a random, block, and alternating copolymer structure. Examples of monomers that can be used for copolymerization include bisphenol compounds in general and hydroxy compounds in general. For example, the aromatic dihydroxy compounds described in paragraph 0014 of JP 2018-154819 A can be mentioned.
[0130] In a polycarbonate having a partial structure (structural unit) represented by general formula (1), the proportion of the structural unit represented by general formula (1) in all structural units excluding both terminals is preferably within the range of 10 to 100 mol %, and more preferably within the range of 40 to 100 mol %.
[0131] The polycarbonate having a partial structure (structural unit) represented by general formula (1) may contain only one type of structural unit other than the structural unit represented by general formula (1), or may contain two or more types of structural units.
[0132] The viscosity average molecular weight (Mv) of the polycarbonate having the partial structure represented by general formula (1) is preferably within the range of 10,000 to 100,000, and more preferably within the range of 20,000 to 50,000. When the viscosity average molecular weight is 10,000 or more, dripping during film-forming by coating can be prevented, and when the viscosity average molecular weight is 100,000 or less, the film thickness uniformity during film-forming by coating can be improved. The viscosity average molecular weight can be measured by the following method.
[0133] (Measurement of Viscosity Average Molecular Weight (Mv)) The viscosity average molecular weight (Mv) of the polycarbonate having the partial structure represented by general formula (1) was calculated from the intrinsic viscosity (η) (unit: dL / g) at 20°C using an Ubbelohde viscometer and using methylene chloride as a solvent, using the following Schnell viscosity formula. η = 1.23 × 10 -4 Mv 0.83
[0134] From the viewpoint of heat resistance due to friction of the photosensitive layer, the glass transition temperature (Tg) of the polycarbonate having the partial structure represented by general formula (1) is preferably within the range of 100 to 300° C. The glass transition temperature (Tg) can be measured by the following method.
[0135] (Measurement of glass transition temperature (Tg)) The glass transition temperature was measured in accordance with JIS K7122 by carrying out two cycles of temperature increase and decrease under the following DSC measurement conditions: A differential scanning calorimeter (DSC, Shimadzu Corporation, "DSC-60") was used as the measuring device. Measurement start temperature: 25℃ Heating rate: 10℃ / min Achieved temperature: 300℃ Cooling rate: 5℃ / min
[0136] The synthesis method of the polycarbonate having the partial structure represented by the general formula (1) is not particularly limited, and a known synthesis method can be used, for example, an interfacial polymerization method, a melt transesterification method, a pyridine method, a ring-opening polymerization method of a cyclic carbonate compound, a solid-phase transesterification method of a prepolymer, etc. Among these, the interfacial polymerization method and the melt transesterification method are preferable.
[0137] The content of the polycarbonate having the partial structure represented by general formula (1) in the binder resin of the outermost layer is preferably within a range of 10 to 100 mass %, and more preferably within a range of 40 to 100 mass %, relative to the total mass of the binder resin.
[0138] (Bisphenol AP type polycarbonate) "Bisphenol AP type polycarbonate" refers to polycarbonate obtained by polymerizing bisphenol AP (1,1-bis(4-hydroxyphenyl)-1-phenylethane) as one of the raw materials. Compared to other polycarbonates, bisphenol AP type polycarbonate has a more rigid binder skeleton, resulting in high filming resistance. Bisphenol AP type polycarbonate has a partial structure represented by the following general formula (1-1).
[0139] [ka]
[0140] The partial structure represented by the general formula (1-1) is a partial structure represented by the general formula (1) in which R1 is a phenyl group, R2 is a methyl group, and R3 to R 10 are hydrogen atoms, respectively.
[0141] In the polycarbonate having a partial structure (structural unit) represented by general formula (1-1), the proportion of the structural unit represented by general formula (1-1) in all structural units excluding both terminals is preferably within the range of 10 to 100 mol %, and more preferably within the range of 40 to 100 mol %.
[0142] The polycarbonate having a partial structure (structural unit) represented by general formula (1-1) may contain only one type of structural unit other than the structural unit represented by general formula (1-1), or may contain two or more types of structural units.
[0143] The viscosity average molecular weight (Mv) of the polycarbonate having the partial structure represented by the general formula (1-1) is preferably within the range of 10,000 to 100,000, and more preferably within the range of 20,000 to 50,000. When the viscosity average molecular weight is 10,000 or more, dripping during film formation can be prevented, and when it is 100,000 or less, the film thickness uniformity during film formation is improved. The viscosity average molecular weight can be measured by the method described above.
[0144] From the viewpoint of heat resistance due to friction of the photosensitive layer, the glass transition temperature (Tg) of the polycarbonate having the partial structure represented by general formula (1) is preferably within the range of 100 to 300° C. The glass transition temperature (Tg) can be measured by the method described above.
[0145] The synthesis method of the polycarbonate having the partial structure represented by the general formula (1-1) is not particularly limited, and a known synthesis method can be used, for example, an interfacial polymerization method, a melt transesterification method, a pyridine method, a ring-opening polymerization method of a cyclic carbonate compound, a solid-phase transesterification method of a prepolymer, etc. Among these, the interfacial polymerization method and the melt transesterification method are preferable.
[0146] (Bisphenol Z type polycarbonate) "Bisphenol Z type polycarbonate" refers to a polycarbonate obtained by polymerizing bisphenol Z (1,1-bis(4-hydroxyphenyl)cyclohexane) as one of the raw materials. By using a polycarbonate having a partial structure represented by the above general formula (1) in combination with bisphenol Z type polycarbonate, micro-crystallization of the resin in a low-temperature environment is suppressed, and high filming resistance is obtained in a low-temperature, low-humidity environment. Bisphenol Z type polycarbonate has a partial structure represented by the following general formula (2).
[0147] [ka]
[0148] The polycarbonate having a partial structure represented by the general formula (2) may be a homopolymer or a copolymer, and the copolymer may have any of a random, block, and alternating copolymer structure. Examples of monomers that can be used for copolymerization include bisphenol compounds in general and hydroxy compounds in general. For example, the aromatic dihydroxy compounds described in paragraph 0014 of JP 2018-154819 A can be mentioned.
[0149] In a polycarbonate having a partial structure (structural unit) represented by general formula (2), the proportion of the structural unit represented by general formula (2) in all structural units excluding both terminals is preferably within the range of 10 to 100 mol %, and more preferably within the range of 40 to 100 mol %.
[0150] The polycarbonate having a partial structure represented by general formula (2) may contain only one type of structural unit other than the structural unit represented by general formula (2), or may contain two or more types of structural units.
[0151] The viscosity average molecular weight (Mv) of the polycarbonate having the partial structure represented by general formula (2) is preferably within the range of 10,000 to 100,000, more preferably within the range of 10,000 to 100,000, and more preferably within the range of 20,000 to 50,000. When the viscosity average molecular weight is 10,000 or more, dripping during film formation can be prevented, and when it is 100,000 or less, the film thickness uniformity during film formation is improved. The viscosity average molecular weight can be measured by the method described above.
[0152] From the viewpoint of heat resistance due to friction of the photosensitive layer, the glass transition temperature (Tg) of the polycarbonate having the partial structure represented by general formula (1) is preferably within the range of 100 to 300° C. The glass transition temperature (Tg) can be measured by the method described above.
[0153] The synthesis method of the polycarbonate having the partial structure represented by the general formula (2) is not particularly limited, and a known synthesis method can be used, for example, an interfacial polymerization method, a melt transesterification method, a pyridine method, a ring-opening polymerization method of a cyclic carbonate compound, a solid-phase transesterification method of a prepolymer, etc. Among these, the interfacial polymerization method and the melt transesterification method are preferable.
[0154] The content of the polycarbonate having a partial structure represented by general formula (2) is preferably within a range of 10 to 90 mass %, and more preferably within a range of 25 to 75 mass %, based on the total mass of the polycarbonate having a partial structure represented by general formula (1).
[0155] (Inorganic fine particles) The outermost layer of the photosensitive layer according to the present invention is characterized by containing inorganic fine particles, which provides abrasion resistance.
[0156] The inorganic fine particles according to the present invention are not particularly limited as long as they are stable compounds in the air, but are preferably insulating oxide particles from the viewpoint of not interfering with the function of the charge transport material. Examples include silica, alumina, magnesium oxide, zirconium oxide, calcium titanate, etc. These may be used alone or in combination of two or more.
[0157] The numerical average particle diameter of the inorganic fine particles is preferably within the range of 5 to 100 nm, and more preferably within the range of 20 to 50 nm. When the numerical average particle diameter is 5 nm or more, the inorganic fine particles are dispersed in a stable state in a coating solution when forming an outermost surface layer. When the numerical average particle diameter is 100 nm or less, the inorganic fine particles are prevented from agglomerating to form coarse particles, and filming resistance is obtained. When the inorganic fine particles are subjected to a surface modification treatment described later, the numerical average particle diameter after the surface modification treatment is preferably within the above range.
[0158] The number primary average particle diameter of the inorganic fine particles in the present invention is defined as the number primary average particle diameter measured by the following method.
[0159] A 10,000x magnified photograph of the sample taken with a scanning electron microscope (manufactured by JEOL Ltd.) is imported into a scanner. Next, 300 inorganic fine particle images, excluding aggregated inorganic fine particles, are randomly binarized using an automatic image processing and analysis system, Luzex AP Software Ver.1.32 (manufactured by Nireco Corporation), from the obtained photographic image, and the horizontal Feret diameter of each of the inorganic fine particle images is calculated. Then, the average value of the horizontal Feret diameters of each of the inorganic fine particle images is calculated to be the number average primary particle size. Here, the "horizontal Feret diameter" refers to the length of the side parallel to the x-axis of the circumscribing rectangle when the inorganic fine particle image is binarized.
[0160] The shape of the inorganic fine particles is not particularly limited, and may be any shape such as powder, sphere, rod, needle, plate, column, irregular shape, scale, spindle shape, and the like.
[0161] The content of the inorganic fine particles is preferably within a range of 5 to 50% by mass, more preferably within a range of 10 to 30% by mass, based on the total mass of the binder resin. When the content is 5% by mass or more, the photoreceptor has sufficient abrasion resistance. When the content is 50% by mass or less, the outermost layer has sufficient strength, and cracks are unlikely to occur.
[0162] (Surface modification treatment) The inorganic fine particles according to the present invention are preferably subjected to a surface modification treatment. The term "surface modification treatment" in the present invention refers to coating the surface of inorganic fine particles with a metal oxide, an organic compound, an organometallic compound, a fluorine compound, a reactive organosilicon compound, or the like, for the purpose of modifying the properties of the particle surface according to purpose, for example, by blocking, reacting, or removing hydroxyl groups present on the surface of the inorganic fine particles. By carrying out surface modification treatment, ozone and NO are reacted with the hydroxyl groups present on the surface of inorganic particles. x It is possible to suppress the decrease in image density and the occurrence of image blur caused by the increase in residual potential caused by the adhesion of active gases such as those mentioned above.
[0163] Whether the surface of inorganic microparticles is coated with metal compounds, organic compounds, organometallic compounds, fluorine compounds, reactive organosilicon compounds, etc. can be confirmed with high precision by a combination of surface analysis techniques such as electron photoelectron spectroscopy (ESCA), Auger electron spectroscopy (Auger), secondary ion mass spectrometry (SIMS), and diffuse reflectance FI-IR.
[0164] The surface modification treatment of inorganic fine particles can be carried out by a wet method. For example, inorganic fine particles are dispersed in water to form an aqueous slurry, and this aqueous slurry is mixed with a water-soluble silicate, a water-soluble aluminum compound, etc. When sodium silicate is used as the water-soluble silicate, it can be neutralized with an acid such as sulfuric acid, nitric acid, or hydrochloric acid. On the other hand, when aluminum sulfate is used as the water-soluble aluminum compound, it can be neutralized with an alkali such as sodium hydroxide or potassium hydroxide.
[0165] In the surface modification treatment using a reactive organosilicon compound, a liquid in which a reactive organosilicon compound is dissolved or suspended in an organic solvent or water is mixed with inorganic fine particles, and the liquid is stirred for several minutes to about an hour. In some cases, the liquid is then subjected to a heat treatment, and then dried through a process such as filtration, to obtain inorganic fine particles whose surfaces are coated with the organosilicon compound.
[0166] In the surface modification treatment using a fluorine compound, a liquid in which an organosilicon compound having fluorine atoms is dissolved or suspended in an organic solvent or water is mixed with inorganic fine particles, and the liquid is stirred for several minutes to about an hour. In some cases, the liquid is then subjected to a heat treatment, and then filtered or dried to obtain inorganic fine particles whose surfaces are coated with a fluorine compound.
[0167] The surface modification treatment may be carried out multiple times. By carrying out the treatment multiple times, the hydrophobicity and hydrophobicity distribution of the oxide particles can be improved, and the decrease in image density, image blur, or transfer memory can be effectively prevented. For example, a surface modification treatment can be carried out in one layer to improve the dispersibility of the inorganic fine particles in the coating liquid, and a surface modification treatment can be carried out in another layer to improve the slipperiness and surface properties of the inorganic fine particles.
[0168] A preferred example of a series of surface modification treatments is one in which a surface modification treatment using a halogenated silane is carried out as a primary treatment, and a surface modification treatment using a silazane compound is carried out as a final treatment.
[0169] Specifically, inorganic fine particles having improved hydrophobicity and hydrophobicity distribution can be obtained by performing a primary treatment with a halogenated silane or silicone oil-based treatment agent, crushing the obtained primary-treated powder, and then performing a secondary treatment with an alkylsilazane-based treatment agent. The primary treatment and secondary treatment may be performed by either a wet method or a dry method.
[0170] As described above, the wet method is a method in which inorganic fine particles and a surface modifier (also called a "surface modification agent") are dispersed in a suitable solvent to attach the surface modifier to the surface of the inorganic fine particles. As a method for dispersing in a solvent, for example, a normal dispersion means such as a ball mill or a sand mill can be used. After the dispersion treatment, the dispersion is dried to remove the solvent, and then a heat treatment is further performed to react and fix the surface modifier to the surface of the inorganic fine particles.
[0171] The dry method is a method in which the surface modifier is attached to the surface of the inorganic fine particles by mixing and kneading the surface modifier and the inorganic fine particles without using a solvent. The other steps are performed in the same manner as in the wet method described above.
[0172] The inorganic fine particles preferably have a hydrophobicity of 76% (vol.%) or more. With a hydrophobicity of 76% (vol.%) or more, the number of hydroxyl groups present on the surface of the inorganic fine particles is reduced, so that the humidity dependency of the potential characteristics (charged potential, residual potential, etc.) is small, and image unevenness due to image blurring and transfer memory is unlikely to occur. The inorganic fine particles more preferably have a hydrophobicity of 80% (vol.%) or more. From the same viewpoint, the inorganic fine particles preferably have a hydrophobicity distribution value of 10% (vol.%) or less.
[0173] In the present invention, the "hydrophobicity (methanol wettability)" is indicated by a scale of wettability with respect to methanol, and is defined as follows.
[0174] Hydrophobicity (vol.%) = (a / (a+50)) x 100 The hydrophobicity and the hydrophobicity distribution can be measured by the following method.
[0175] (Method of measuring hydrophobicity) 0.2 g of the inorganic particles to be measured is weighed and added to 50 mL of distilled water in a 200 mL beaker. Next, methanol is slowly dripped from a burette with the tip immersed in the liquid while slowly stirring until the inorganic particles are completely wet (until all of them have settled). The amount of methanol required to completely wet the inorganic particles is designated as a (mL), and the hydrophobicity is calculated using the above formula.
[0176] (Method of measuring hydrophobicity distribution value) 1) Weigh out 0.2 g of the inorganic particles to be measured and place them in a centrifuge tube. Prepare one more sample tube (for total centrifugation) than the number of points to be plotted. 2) Using a Komagome pipette, place 7 ml of each of the different concentrations of methanol solution into a centrifuge tube and close tightly. For total precipitation, use the methanol concentration determined by the hydrophobicity measurement method described above. 3) Disperse using a Turbula mixer (90 rpm, 30 seconds). 4) Centrifuge (3500 rpm, 10 minutes). 5) Read the sedimentation volume and calculate the percentage of each sedimentation volume when the total sedimentation volume (volume when everything has settled) is 100%. 6) Based on the above measured values, create a graph (hydrophobicity distribution curve) with the methanol concentration (Vol.%) on the horizontal axis and the sedimentation volume (Vol.%) on the vertical axis.
[0177] The hydrophobicity distribution value is defined as follows:
[0178] The hydrophobicity distribution curve is shown in Figure 4. In the distribution curve in Figure 4, the methanol concentration at point a represents the hydrophobicity, and the difference between the methanol concentration at point a and the methanol concentration at point b; Δ(ab) represents the hydrophobicity distribution value in the present invention, which is preferably 25 or less.
[0179] Examples of silicone oil-based treatment agents preferably used for primary treatment include straight silicone oils such as dimethyl silicone oil, methylphenyl silicone oil, and methylhydrogen silicone oil, and modified silicone oils such as amino-modified silicone oil, epoxy-modified silicone oil, carboxyl-modified silicone oil, carbinol-modified silicone oil, methacryl-modified silicone oil, mercapto-modified silicone oil, phenol-modified silicone oil, one-end reactive modified silicone oil, heterogeneous functional group modified silicone oil, polyether-modified silicone oil, methylstyryl-modified silicone oil, alkyl-modified silicone oil, higher fatty acid ester-modified silicone oil, hydrophilic special modified silicone oil, higher alkoxy-modified silicone oil, higher fatty acid-containing modified silicone oil, and fluorine-modified silicone oil. These may be used alone or in combination of two or more.
[0180] Examples of halogenated silanes include dimethyldichlorosilane, monochlorosilane, dichlorosilane, trichlorosilane, and tetrachlorosilane.
[0181] Examples of silazanes preferably used in the final treatment include hexamethyldisilazane, hexaethyldisilazane, hexapropyldisilazane, hexabutyldisilazane, hexapentyldisilazane, hexahexyldisilazane, hexacyclohexyldisilazane, hexaphenyldisilazane, divinyltetramethyldisilazane, and dimethyltetravinyldisilazane.
[0182] In addition to the above silicone oil-based treatment agents and halogenated silanes, the following alkoxysilanes, siloxanes, metal alkoxides, fatty acids and their metal salts, etc. may be used as surface modifiers before the final treatment with silazanes.
[0183] Examples of alkoxysilanes include tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, o-methylphenyltrimethoxysilane, p-methylphenyltrimethoxysilane, n-butyltrimethoxysilane, i-butyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, and phenyltriethoxy. Silane, diphenyldiethoxysilane, i-butyltriethoxysilane, decyltriethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, and the like.
[0184] Examples of the siloxanes include hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, hexamethyldisiloxane, and octamethyltrisiloxane.
[0185] Examples of metal alkoxides include trimethoxyaluminum, triethoxyaluminum, tri-i-propoxyaluminum, tri-n-butoxyaluminum, tri-s-butoxyaluminum, tri-t-butoxyaluminum, mono-s-butoxydi-i-propylaluminum, tetramethoxytitanium, tetraethoxytitanium, tetra-i-propoxytitanium, tetra-n-propoxytitanium, tetra-n-butoxytitanium, tetra-s-butoxytitanium, tetra-t-butoxytitanium, tetraethoxyzirconium, tetra-i-propoxyzirconium, tetra-n-butoxyzirconium, dimethoxytin, diethoxytin, di-n-butoxytin, tetraethoxytin, tetra-i-propoxytin, tetra-n-butoxytin, diethoxyzinc, magnesium methoxide, magnesium ethoxide, and magnesium isopropoxide.
[0186] Examples of fatty acids and their metal salts include long-chain fatty acids such as undecylic acid, lauric acid, tridecylic acid, dodecylic acid, myristic acid, palmitic acid, pentadecylic acid, stearic acid, heptadecylic acid, arachidic acid, montanic acid, oleic acid, linoleic acid, and arachidonic acid, and examples of their metal salts include salts with metals such as zinc, iron, magnesium, aluminum, calcium, sodium, and lithium.
[0187] These surface modifiers are preferably used after diluting with hexane, toluene, alcohol (eg, methanol, ethanol, propanol), acetone, or the like, or, in some cases, water.
[0188] From the viewpoint of uniform dispersion in the binder resin, the inorganic fine particles according to the present invention are preferably silica that has been hydrophobized by a surface modification treatment.
[0189] It is preferable to perform calcination strengthening on inorganic fine particles. In particular, when silica is used, it is difficult to perform hydrophobic treatment on silica that has not been calcined strengthened, so calcined strengthened silica is preferable as the silica to be subjected to surface modification treatment. Calcined strengthened silica is usually calcined at a temperature of 500°C or higher, preferably 1000°C or higher, in order to provide sufficient strength. The calcination time is preferably 5 hours or more, more preferably 10 hours or more.
[0190] By calcining silica under the above calcination conditions, functional groups such as hydroxyl groups and silanol groups present on the surface of silica particles are decomposed to form silicon oxides. As a result, the specific surface area of the silica particles is reduced, and when the silica particles are subjected to hydrophobic treatment using a silane compound or the like, the surface can be effectively modified. Specific examples of such silica include those produced by high-temperature hydrolysis of silicon tetrachloride in an oxygen flame.
[0191] An example of the procedure for the surface modification treatment to obtain the hydrophobic silica preferably used in the present invention will be given below. Silica powder is reacted in a solvent containing silicone oil (preferably adjusted to pH 4 at 25°C with an organic acid or the like), the solvent is then removed, and a crushing treatment is then carried out. The crushed treated powder is then reacted in a solvent containing a silazane compound, the solvent is then removed, and a crushing treatment is then carried out.
[0192] Alternatively, the following method may be used: silica powder is placed in a reaction tank, and alcohol water is added under a nitrogen atmosphere while stirring, a silicone oil-based treatment liquid such as organopolysiloxane is introduced into the reaction tank to perform surface modification treatment, and the solvent is removed by heating and stirring. After that, after a disintegration treatment, an alkylsilazane-based treatment liquid is introduced under a nitrogen atmosphere while stirring to perform surface modification treatment, and the solvent is removed by heating and stirring, and then the mixture is cooled. By appropriately changing the treatment conditions, the hydrophobicity and hydrophobicity distribution value of the silica powder can be adjusted to within the above range.
[0193] The method for producing the inorganic fine particles according to the present invention is not particularly limited, and they can be produced by a known method. In addition, commercially available products can be used, and examples of hydrophobic silica include AEROSIL (registered trademark) RX50, R40SX300, NAX50, VP RX40S, SX110, etc., manufactured by Nippon Aerosil Co., Ltd. Examples of alumina include AEROSIL (registered trademark) RXC65K1, etc., manufactured by Nippon Aerosil Co., Ltd.
[0194] (charge transport material) The outermost layer of the photosensitive layer according to the present invention is characterized by containing a charge transport material, which makes it possible to form an electrostatic latent image on the surface of the photoreceptor. The term "charge transport material" (also referred to as "charge transport substance") refers to a material that transports electric charges (holes).
[0195] The charge transport material according to the present invention is not particularly limited, and known compounds can be used, including carbazole derivatives, oxazole derivatives, oxadiazole derivatives, thiazole derivatives, thiadiazole derivatives, triazole derivatives, imidazole derivatives, imidazolone derivatives, imidazolidine derivatives, bisimidazolidine derivatives, styryl compounds, hydrazone compounds, pyrazoline compounds, oxazolone derivatives, benzimidazole derivatives, quinazoline derivatives, benzofuran derivatives, acridine derivatives, phenazine derivatives, aminostilbene derivatives, triarylamine derivatives, phenylenediamine derivatives, stilbene derivatives, benzidine derivatives, poly-N-vinylcarbazole, poly-1-vinylpyrene, and poly-9-vinylanthracene. These may be used alone or in combination of two or more.
[0196] The content of the charge transport material is preferably within a range of 30 to 200% by mass, and more preferably within a range of 50 to 150% by mass, based on the total mass of the binder resin.
[0197] (Other additives) The outermost layer of the photosensitive layer according to the present invention may contain other additives, and preferably contains, for example, an antioxidant, lubricant particles, etc. By containing an antioxidant in the outermost layer, the action of oxygen on autoxidizing substances present in the photoreceptor or on the surface of the photoreceptor (the outermost layer of the photosensitive layer) under conditions of light, heat, discharge, etc. can be prevented or suppressed.
[0198] The antioxidant is not particularly limited, and any known antioxidant can be used. For example, the antioxidants described in JP-A-2006-301247 can be used.
[0199] The lubricant particles for the outermost layer of the photosensitive layer are not particularly limited, and for example, fluorine atom-containing resin particles can be used. The fluorine atom-containing resin particles are not particularly limited, and examples thereof include tetrafluoroethylene resin, trifluorochloroethylene resin, hexafluorochloroethylene propylene resin, vinyl fluoride resin, vinylidene fluoride resin, difluorodichloroethylene resin, and copolymers thereof. These may be used alone or in combination of two or more. Among these, tetrafluoroethylene resin and vinylidene fluoride resin are particularly preferred.
[0200] (Method of forming outermost surface layer) The outermost layer of the photosensitive layer according to the present invention is formed by dissolving the above-mentioned binder resin and charge transport material in a solvent and dispersing inorganic fine particles in a coating solution, applying the solution to form the outermost layer of the photosensitive layer by a known method, and then naturally drying or heating the solution.
[0201] The solvent for dissolving the binder resin and the charge transport material is not particularly limited, and examples thereof include toluene, xylene, methyl ethyl ketone, cyclohexanone, ethyl acetate, butyl acetate, methanol, ethanol, propanol, butanol, tetrahydrofuran, 1,4-dioxane, and 1,3-dioxolane.
[0202] Preferred coating methods include coating with a slide hopper type device, dip coating, spray coating, etc. In particular, coating with a circular slide hopper type device, which is described in detail in JP-A-58-189061, etc., is preferred.
[0203] In the coating method using a circular slide hopper type device, the end of the slide surface and the substrate are arranged with a certain gap (about 2 μm to 2 mm), so coating can be performed without damaging the substrate, and even when layers with different properties are formed in multiple layers, coating can be performed without damaging the layers already coated. Furthermore, even when layers with different properties that dissolve in the same solvent are formed in multiple layers, the time that the laminate remains in the solvent is much shorter than in the dip coating method, so that the components of the lower layer hardly dissolve into the upper layer side, and can be coated without dissolving into the coating layer, so coating can be performed without deteriorating the dispersibility of the inorganic fine particles.
[0204] <3.1.2 Protective layer> The photosensitive layer according to the present invention preferably has a protective layer, and in this case, the protective layer corresponds to the outermost layer of the photosensitive layer. The protective layer protects the surface of the photoreceptor, improves abrasion resistance and scratch resistance, reduces the occurrence of toner slippage, and contributes to extending the life of the photoreceptor and, ultimately, the image forming apparatus. In addition, by providing the protective layer, the variation in thickness of the photosensitive layer is reduced, thereby improving the rate of non-defective products (productivity).
[0205] The thickness of the protective layer is preferably within the range of 1 to 30 μm, and more preferably within the range of 5 to 20 μm.
[0206] The protective layer may further contain an antioxidant, an electronic conductive agent, a stabilizer, silicone oil, etc. As the antioxidant, those disclosed in JP-A-2000-305291 and as the electronic conductive agent, those disclosed in JP-A-50-137543 and JP-A-58-76483 are preferred.
[0207] <3.1.3 Charge transport layer> The term "charge transport layer" refers to a layer containing a charge transport material. Therefore, the protective layer is also included in the charge transport layer, but in the present invention, when the layer containing the charge transport material is only one layer, the layer is regarded as the charge transport layer, and when the layer contains two layers, the layer on the outermost surface side is regarded as the protective layer, and the layer on the conductive support side is regarded as the charge transport layer. By forming the layer containing the charge transport material in two layers, the variation in thickness is reduced.
[0208] Therefore, when the photosensitive layer does not have a protective layer, that is, when there is only one layer containing a charge transport material, the charge transport layer corresponds to the outermost layer of the above-mentioned photosensitive layer.
[0209] The charge transport layer in the case where the photosensitive layer has a protective layer will be described below.
[0210] An example of the charge transport layer is a structure in which a charge transport material is dispersed in a binder resin. Examples of the charge transport material of the charge transport layer include substances that transport charges (holes), such as triphenylamine derivatives, hydrazone compounds, styryl compounds, benzidine compounds, and butadiene compounds.
[0211] In addition, when the photosensitive layer has a protective layer, the charge transport layer preferably contains a charge transport material with high mobility and large molecular weight.As such a charge transport material, known compounds can be used in combination, such as carbazole derivatives, oxazole derivatives, oxadiazole derivatives, thiazole derivatives, thiadiazole derivatives, triazole derivatives, imidazole derivatives, imidazolone derivatives, imidazolidine derivatives, bisimidazolidine derivatives, hydrazone compounds, pyrazoline compounds, oxazolone derivatives, benzimidazole derivatives, quinazoline derivatives, benzofuran derivatives, acridine derivatives, phenazine derivatives, aminostilbene derivatives, triarylamine derivatives, phenylenediamine derivatives, stilbene derivatives, poly-N-vinylcarbazole, poly-1-vinylpyrene and poly-9-vinylanthracene.These compounds may be used alone or in combination of two or more.
[0212] The binder resin is not particularly limited, and known resins can be used, such as polycarbonate resin, polyacrylate resin, polyester resin, polystyrene resin, styrene-acrylonitrile copolymer, polymethacrylic acid ester resin, styrene-methacrylic acid ester copolymer, etc., and polycarbonate resin is particularly preferred. Furthermore, from the viewpoint of crack resistance, abrasion resistance, and electrostatic properties, bisphenol A type, bisphenol Z type, dimethyl bisphenol A type, bisphenol A type-dimethyl bisphenol A type copolymer type polycarbonate resin, etc. are preferred. These may be used alone or in combination of two or more.
[0213] The content of the charge transport material in the charge transport layer is preferably within a range of 10 to 500% by mass, and more preferably within a range of 20 to 250% by mass, based on the total mass of the binder resin.
[0214] The thickness of the charge transport layer is preferably within the range of 10 to 50 μm, and more preferably within the range of 15 to 40 μm.
[0215] The charge transport layer may further contain an antioxidant, an electronic conductive agent, a stabilizer, silicone oil, etc. The antioxidant is preferably one disclosed in JP-A-2000-305291, and the electronic conductive agent is preferably one disclosed in JP-A-50-137543 and JP-A-58-76483.
[0216] The charge transport layer can be formed by the same method as the method for forming the outermost layer of the photosensitive layer described above. From the viewpoint of improving productivity in the region of a film thickness of 20 to 50 μm, the charge transport layer is preferably applied by a dip coating method.
[0217] The charge transport layer can also be formed by vacuum deposition of the charge transport material, in which case the binder resin is not necessarily used.
[0218] <3.1.4 Charge generation layer> The term "charge generation layer" refers to a layer containing a charge generation material. One example of the charge generation layer is one in which the charge generation material is dispersed in a binder resin.
[0219] The charge generating material is not particularly limited, and examples thereof include azo raw materials such as Sudan Red and Diane Blue, quinone pigments such as pyrenequinone and anthanthrone, quinocyanine pigments, perylene pigments, indigo pigments such as indigo and thioindigo, polycyclic quinone pigments such as pyranthrone and diphthaloylpyrene, and phthalocyanine pigments. In particular, polycyclic quinone pigments and titanyl phthalocyanine pigments are preferred. These may be used alone or in combination of two or more.
[0220] The binder resin is not particularly limited, and known resins can be used, such as polystyrene resin, polyethylene resin, polypropylene resin, acrylic resin, methacrylic resin, vinyl chloride resin, vinyl acetate resin, polyvinyl butyral resin, epoxy resin, polyurethane resin, phenol resin, polyester resin, alkyd resin, polycarbonate resin, silicone resin, melamine resin, and copolymers containing two or more of these resins (for example, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinyl acetate-maleic anhydride copolymer), polyvinylcarbazole resin, etc., and polyvinyl butyral resin is particularly preferred. These may be used alone or in combination of two or more.
[0221] The content of the charge generating material in the charge generating layer is preferably within the range of 1 to 600% by mass, more preferably within the range of 50 to 500% by mass, based on the total mass of the binder resin. By being within the above range, high dispersion stability can be obtained in the coating liquid for forming the charge generating layer. In addition, since a photoreceptor with relatively low electrical resistance is obtained, the increase in residual potential that occurs with repeated use can be suppressed.
[0222] The thickness of the charge generating layer is preferably within the range of 0.01 to 5 μm, and more preferably within the range of 0.05 to 3 μm.
[0223] The charge generating layer is formed by preparing a coating solution in which a binder resin is dissolved in a solvent and a charge generating material is dispersed, coating the coating solution by a known method, and then naturally drying or heating.
[0224] The solvent for dissolving the binder resin is not particularly limited, and examples thereof include toluene, xylene, methyl ethyl ketone, cyclohexane, ethyl acetate, butyl acetate, methanol, ethanol, propanol, butanol, methyl cellosolve, ethyl cellosolve, tetrahydrofuran, 1-dioxane, 1,3-dioxolane, pyridine, and diethylamine.
[0225] The means for dispersing the charge generating material is not particularly limited, and examples thereof include an ultrasonic disperser, a ball mill, a sand grinder, and a homomixer.
[0226] By filtering the coating solution to remove foreign matter or aggregates before coating, the occurrence of image defects can be prevented. As the coating method, the same coating method as that for the charge transport layer described above can be used.
[0227] The charge generating layer can also be formed by vacuum deposition of the charge generating material, in which case the binder resin is not necessarily used.
[0228] In addition, the charge generation layer and the charge transport layer can be formed as a single layer by containing the charge generation material and the charge transport material in the same layer. One example of such a single layer is a structure in which the charge generation material and the charge transport material are dispersed in a binder resin. The binder resin is not particularly limited, and the same binder resin as that used in the charge generation layer can be used.
[0229] In the case of the single layer structure, the thickness of the single layer is preferably within the range of 10 to 50 μm, and more preferably within the range of 20 to 40 μm.
[0230] <3.2 Conductive support> The conductive support according to the present invention is not particularly limited as long as it is conductive, and examples thereof include metals such as aluminum, copper, chromium, nickel, zinc, and stainless steel formed into a drum or sheet shape, metal foils such as aluminum and copper laminated onto plastic films, plastic films onto which aluminum, indium oxide, tin oxide, and the like are vapor-deposited, and metals, plastic films, and papers on which a conductive layer is provided by applying a conductive substance alone or together with a binder resin.
[0231] <3.3 Middle class> The photoreceptor according to the present invention may have an intermediate layer between the conductive support and the photosensitive layer, the intermediate layer having a barrier function and an adhesive function. Considering prevention of various failures, it is preferable to provide the intermediate layer. One example of the intermediate layer is a structure in which conductive particles or metal oxide particles are contained in a binder resin as necessary.
[0232] The binder resin is not particularly limited, and examples thereof include casein, polyvinyl alcohol, nitrocellulose, ethylene-acrylic acid copolymer, polyamide resin, polyurethane resin, gelatin, etc., and alcohol-soluble polyamide resin is particularly preferred. These may be used alone or in combination of two or more.
[0233] The intermediate layer can contain various conductive particles or metal oxide particles for the purpose of adjusting electrical resistance. For example, various metal oxide particles such as alumina, zinc oxide, titanium oxide, tin oxide, antimony oxide, indium oxide, and bismuth oxide can be used. In addition, conductive particles (ultrafine particles) such as tin-doped indium oxide, antimony-doped tin oxide, and zirconium oxide can be used.
[0234] The number average primary particle size of such conductive particles or metal oxide particles is preferably 0.3 μm or less, and more preferably 0.1 μm or less.
[0235] These conductive particles or metal oxide particles may be used alone or in combination of two or more kinds. When two or more kinds are used in combination, they may be in the form of a solid solution or fusion.
[0236] The content of the conductive particles or metal oxide particles is preferably within a range of 20 to 400 mass %, and more preferably within a range of 50 to 350 mass %, based on the total mass of the binder resin.
[0237] From the viewpoint of adjusting the electrical resistance, the thickness of the intermediate layer is preferably within a range of 0.1 to 15 μm, and more preferably within a range of 0.3 to 10 μm.
[0238] The intermediate layer is formed by preparing a coating solution in which a binder resin is dissolved in a solvent and conductive particles or metal oxide particles are dispersed, coating the coating solution by a known method, and then naturally drying or heating.
[0239] The solvent for dissolving the binder resin is not particularly limited, and it is preferable that the conductive particles or metal oxide particles are well dispersed and the binder resin such as polyamide resin is dissolved in the solvent. For example, alcohols having 2 to 4 carbon atoms such as ethanol, n-propyl alcohol, isopropyl alcohol, n-butanol, t-butanol, and sec-butanol can be mentioned. These may be used alone or in combination of two or more.
[0240] From the viewpoint of improving the storage stability of the coating liquid and the dispersibility of the particles, a co-solvent can be used in combination. Examples of the co-solvent include methanol, benzyl alcohol, toluene, cyclohexanone, and tetrahydrofuran.
[0241] The concentration of the binder resin in the coating liquid can be appropriately selected according to the thickness of the intermediate layer and the coating method. The content of the conductive particles or metal oxide particles in the coating liquid is preferably within a range of 20 to 400% by mass, more preferably within a range of 50 to 200% by mass, based on the total mass of the binder resin.
[0242] The means for dispersing the charge generating material is not particularly limited, and examples thereof include an ultrasonic disperser, a ball mill, a sand grinder, a homomixer, etc. The coating method may be the same as the coating method for the charge transport layer described above.
[0243] <3.4 Photoconductor manufacturing method> The photoreceptor according to the present invention is preferably produced by a production method including a step (step (4) below) of applying a solution containing a polycarbonate having a partial structure represented by the above general formula (1), inorganic fine particles, and a charge transport material, and further including the following steps (1) to (3).
[0244] In the photoreceptor according to the present invention, the outermost layer of the photosensitive layer contains a polycarbonate having a partial structure represented by the above general formula (1) having a relatively rigid skeleton. Therefore, even if the outermost layer is formed by coating and drying, inorganic fine particles are unlikely to aggregate, unevenness on the photoreceptor surface is reduced, and the filming phenomenon can be suppressed.
[0245] Step (1): A step of forming an intermediate layer by applying a coating liquid for forming an intermediate layer to the outer peripheral surface of a conductive support and drying the coating liquid. Step (2): A step of forming a charge generating layer by applying a coating liquid for forming a charge generating layer to the outer peripheral surface of the conductive support or the outer peripheral surface of the intermediate layer formed in step (1) and drying the coating liquid. Step (3): A step of forming a charge transport layer by applying a coating liquid for forming a charge transport layer to the outer peripheral surface of the charge generating layer formed in step (2) and drying the coating liquid. Step (4): A step of forming an outermost layer by applying a coating liquid for forming an outermost layer to the outer peripheral surface of the charge generating layer formed in step (2) or the outer peripheral surface of the charge transport layer formed in step (3) and drying the coating liquid.
[0246] In the coating liquid for forming each layer, the concentration of each component is appropriately selected according to the thickness and production speed of each layer.
[0247] In the coating liquid for forming each layer, the means for dispersing the inorganic fine particles and charge generating material contained in the outermost layer, the conductive particles or metal oxide particles contained in the intermediate layer, etc. is not particularly limited, and an ultrasonic disperser, a ball mill, a sand mill, a homomixer, etc. can be used.
[0248] The method for applying the coating liquid for forming each layer is not particularly limited, and examples thereof include known methods such as a dip coating method, a spray coating method, a spinner coating method, a bead coating method, a blade coating method, a beam coating method, a slide hopper method, and a circular slide hopper method.
[0249] The method for drying the coating film can be appropriately selected depending on the type of solvent and the thickness of the layer, but natural drying or heating is preferred.
[0250] The steps of forming each layer will be described in detail below.
[0251] <Step (1): Formation of intermediate layer> The intermediate layer can be formed by dissolving a binder resin for the intermediate layer in a solvent to prepare a coating liquid for forming the intermediate layer, dispersing or dissolving other components such as conductive particles or metal oxide particles, a dispersant, a leveling agent, etc. as necessary, applying the coating liquid to a certain thickness on a conductive support to form a coating film, and drying the coating liquid. The coating liquid for forming the intermediate layer is preferably applied by a dip coating method.
[0252] <Step (2): Formation of Charge Generation Layer> The charge generation layer can be formed by dispersing a charge generation material in a solution in which a binder resin for the charge generation layer is dissolved in a solvent to prepare a coating liquid for forming the charge generation layer, applying the coating liquid to a certain thickness on a conductive support or an intermediate layer to form a coating film, and drying the coating liquid. The coating liquid for forming the charge generation layer is preferably applied by a dip coating method.
[0253] Step (3): Formation of Charge Transport Layer Step (3) is a step of forming a charge transport layer when the photoreceptor has a protective layer. The charge transport layer can be formed by dissolving a binder resin and a charge transport material in a solvent to prepare a coating liquid for forming the charge transport layer, applying the coating liquid to a certain thickness on the charge generating layer to form a coating film, and drying the coating liquid. The coating liquid for forming the charge transport layer is preferably applied by a dip coating method.
[0254] <Step (4): Formation of outermost layer> The outermost layer can be formed by adding a polycarbonate having a partial structure represented by the above general formula (1), inorganic fine particles, and a charge transport material to a known solvent to prepare a coating liquid for forming the outermost layer, applying the coating liquid for forming the outermost layer to the outer peripheral surface of the charge generating layer or the outer peripheral surface of the charge transport layer to form a coating film, and drying the coating liquid. The coating liquid for forming the outermost layer is preferably applied by a slide hopper method using a circular slide hopper coating device, and can be applied by the method disclosed in, for example, JP-A-2015-114454.
[0255] <4 Image forming device> As described above, in the image forming system of the present invention, the device section is particularly called the "image forming apparatus." That is, the image forming apparatus according to the present invention is characterized by comprising a photoconductor, a charging unit, an exposure unit, a developing unit, a transfer unit, and a cleaning unit, and further comprising a fogging toner supply mechanism.
[0256] Fig. 5 is an explanatory cross-sectional view showing an example of the configuration of an image forming apparatus according to the present invention, and Fig. 6 is an explanatory cross-sectional view showing an example of the configuration of a main part of the image forming apparatus according to the present invention.
[0257] The image forming apparatus 100 shown in FIG. 5 is called a tandem type color image forming apparatus, and has four image forming units 110Y, 110M, 110C, and 110Bk, a paper feeding and conveying means 150, and a fixing means 170.
[0258] An original image reading device SC is disposed on the upper portion of the main body of the image forming apparatus 100.
[0259] The image forming units 110Y, 110M, 110C, and 110Bk are arranged side by side in the vertical direction.
[0260] The image forming units 110Y, 110M, 110C, and 110Bk each include a rotating drum-shaped photoconductor 111Y, 111M, 111C, and 111Bk, charging means 113Y, 113M, 113C, and 113Bk, exposure means 115Y, 115M, 115C, and 115Bk, developing means 117Y, 117M, 117C, and 117Bk, primary transfer rollers (primary transfer means) 133Y, 133M, 133C, and 133Bk, and cleaning means 119Y, 119M, 119C, and 119Bk, which are arranged sequentially in the rotational direction of the photoconductor in the outer circumferential surface area.
[0261] A configuration is adopted in which toner images of yellow (Y), magenta (M), cyan (C) and black (Bk) are formed on the photoconductors 111Y, 111M, 111C and 111Bk, respectively.
[0262] Hereinafter, the components of the image forming apparatus other than the photoconductor will be described. Note that when the drawings are used, the image forming unit 110Y will be taken as an example.
[0263] <4.1 Charging means> The charging means is a means for uniformly charging the surface of the photoreceptor.
[0264] Charging means include contact types such as charging rollers, charging brushes, and charging blades, and non-contact types such as corona chargers (corotron chargers, strocotton chargers, etc.). Contact types have the advantage of generating less harmful ozone gas during the charging process. Non-contact types have the advantage of being less prone to filming than contact types because they are not close-proximity discharges.
[0265] The charging means of the image forming system of the present invention may be of a contact type or a non-contact type. Since the image forming system of the present invention has enhanced filming resistance due to the effects of the photoconductor, the lubricant, and the fogging toner supply mechanism, it is preferable that the charging means be of a contact type from the viewpoint of the amount of ozone gas generated.
[0266] 5 and 6 is a contact type charging unit 113Y. The charging unit 113Y in this example is made up of a charging roller arranged in contact with the surface of the photoconductor 111Y and a power source that applies a voltage to the charging roller.
[0267] An example of a contact-type charging means will be described. The charging roller 11 shown in Fig. 7 has a configuration in which a resistance control layer 11c for obtaining a high uniform electrical resistance as a whole of the charging roller 11 is laminated on the surface of an elastic layer 11b for reducing charging noise and imparting elasticity to obtain uniform adhesion to the photoconductor 111Y, which is laminated on the surface of a core metal 11a, as necessary, and a surface layer 11d is laminated on the resistance control layer 11c, which is biased by a pressing spring 11e in the direction of the photoconductor 111Y and pressed against the surface of the photoconductor 111Y with a predetermined pressing force to form a charging nip portion, and the charging roller 11 rotates following the rotation of the photoconductor 111Y.
[0268] The core metal 11a is made of a metal such as iron, copper, stainless steel, aluminum or nickel, or the surface of such a metal is plated to provide rust resistance and scratch resistance without impairing electrical conductivity, and its outer diameter is, for example, within the range of 3 to 20 mm.
[0269] The elastic layer 11b is made of an elastic material such as rubber to which conductive particles such as carbon black, carbon graphite, or conductive particles such as alkali metal salts or ammonium salts are added.
[0270] Specific examples of elastic materials include synthetic rubbers such as natural rubber, ethylene propylene diene methylene rubber (EPDM), styrene-butadiene rubber (SBR), silicone rubber, urethane rubber, epichlorohydrin rubber, isoprene rubber (IR), butadiene rubber (BR), nitrile-butadiene rubber (NBR), and chloroprene rubber (CR), resins such as polyamide resin, polyurethane resin, silicone resin, and fluororesin, and foams such as foamed sponge, etc. The degree of elasticity can be adjusted by adding process oil, plasticizer, etc. to the elastic material.
[0271] The volume resistivity of the elastic layer 11b is 1×10 1 ~1×10 10 The volume resistivity of the elastic layer 11b is preferably in the range of Ω·cm.
[0272] The thickness of the elastic layer 11b is preferably within a range of 500 to 5000 μm, and more preferably within a range of 500 to 3000 μm.
[0273] The resistance control layer 11c is provided for the purpose of providing uniform electrical resistance throughout the charging roller 11, but may not be provided. The resistance control layer 11c can be provided by coating a material having appropriate electrical conductivity or by covering the layer with a tube having appropriate electrical conductivity.
[0274] Specific materials constituting the resistance control layer 11c include resins such as polyamide resin, polyurethane resin, fluororesin, and silicone resin; and rubbers such as epichlorohydrin rubber, urethane rubber, chloroprene rubber, and acrylonitrile-based rubber, to which conductive agents such as conductive fine particles made of carbon black, carbon graphite, etc.; conductive metal oxide fine particles made of conductive titanium oxide, conductive zinc oxide, conductive tin oxide, etc.; and conductive fine particles made of alkali metal salts, ammonium salts, etc. have been added.
[0275] The volume resistivity of the resistance control layer 11c is 1×10 -2 ~1×10 14 It is preferably in the range of Ω·cm, and more preferably 1×10 1 ~1×10 10 The volume resistivity of the resistance control layer 11c is in the range of Ω·cm.
[0276] The thickness of the resistance control layer 11c is preferably within a range of 0.5 to 100 μm, more preferably within a range of 1 to 50 μm, and further preferably within a range of 1 to 20 μm.
[0277] The surface layer 11d is provided for the purposes of preventing the plasticizer in the elastic layer 11b from bleeding out onto the surface of the resulting charging roller, of obtaining slipperiness and smoothness on the surface of the charging roller, and of preventing the occurrence of leaks even if there are defects such as pinholes on the photoconductor 111Y, and is provided by coating the surface with a material having appropriate electrical conductivity or by covering it with a tube having appropriate electrical conductivity.
[0278] When the surface layer 11d is provided by coating a material, a specific example of the material is polyamide resin. Examples of such conductive materials include conductive fine particles made of carbon black, carbon graphite, etc.; and conductive metal oxide fine particles made of conductive titanium oxide, conductive zinc oxide, conductive tin oxide, etc., added to a base material such as a resin such as grease, polyurethane resin, acrylic resin, fluororesin, or silicone resin, or epichlorohydrin rubber, urethane rubber, chloroprene rubber, or acrylonitrile-based rubber. Examples of the coating method include a dip coating method, a roll coating method, and a spray coating method.
[0279] In addition, when the surface layer 11d is provided by covering with a tube, specific examples of the tube include nylon 12, tetrafluoroethylene-perfluoroalkylvinylether copolymer resin (PFA), polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer resin (FEP), and thermoplastic elastomers such as polystyrene, polyolefin, polyvinyl chloride, polyurethane, polyester, and polyamide, to which the above-mentioned conductive agent is added, molded into a tube shape. This tube may be either heat-shrinkable or non-heat-shrinkable.
[0280] The volume resistivity of the surface layer 11d is 1×10 1 ~1×10 8 It is preferably in the range of Ω·cm, and more preferably 1×10 1 ~1×10 5 The volume resistivity of the surface layer 11d is a value measured in accordance with JIS K 6911.
[0281] The thickness of the surface layer 11d is preferably within a range of 0.5 to 100 μm, more preferably within a range of 1 to 50 μm, and further preferably within a range of 1 to 20 μm.
[0282] The surface roughness of the surface layer 11d is preferably within a range of 1 to 30 μm, more preferably within a range of 2 to 20 μm, and further preferably within a range of 5 to 10 μm.
[0283] In the charging roller 11 as described above, a charging bias voltage is applied to the core metal 11a of the charging roller 11 from the power source S1, whereby the surface of the photoconductor 111Y is charged to a predetermined potential of a predetermined polarity.
[0284] Here, the charging bias voltage may be, for example, only a DC voltage, but it is preferable that it be an oscillating voltage in which an AC voltage is superimposed on a DC voltage, as this provides excellent charging uniformity.
[0285] <4.2 Exposure means> The exposure unit is a unit that exposes the photoconductor, to which a uniform potential has been applied by the charging unit, based on an image signal, to form an electrostatic latent image corresponding to the image.
[0286] Examples of the exposure means include a means consisting of an LED in which light emitting elements are arranged in an array in the axial direction of the photoconductor, and an imaging element, and a laser optical system.
[0287] <4.3 Developing method> The developing means (developing machine) is a means for supplying toner to the surface of the photoconductor to develop the electrostatic latent image formed on the surface of the photoconductor, thereby forming a toner image.
[0288] The developing means 117Y shown in FIG. 5 is specifically composed of a developing roller 118Y that has a built-in magnet and rotates while holding a developer, and a voltage application device (not shown) that applies a DC and / or AC bias voltage between the photoconductor 111Y and the developing roller 118Y.
[0289] The toner is transported to the photoconductor 111Y by the rotation of the developing roller 118Y. Then, a thin layer of toner on the developing roller 118Y comes into contact with the photoconductor 111Y to develop the electrostatic latent image on the photoconductor 111Y.
[0290] The developing roller 118Y is connected to a voltage application device. This voltage application device applies a DC and / or AC bias voltage to the developing roller 118Y. The developing bias can be adjusted to a desired value by controlling the voltage applied to the developing roller 118Y.
[0291] Due to a potential difference (development potential difference) between the potential of the electrostatic latent image carried by the developing roller 118Y and the photoconductor 111Y, an electric field is formed in a developing section where the developing roller 118Y and the photoconductor 111Y face each other.
[0292] The toner in the developer transported to the developing section by the rotation of the developing roller 118Y moves due to the force of the electric field and is attracted to the electrostatic latent image on the photoreceptor 111Y. The electrostatic latent image carried on the photoreceptor 111Y is visualized, and a toner image corresponding to the shape of the electrostatic latent image is formed on the surface of the photoreceptor 111Y.
[0293] <4.4 Transfer Method> The transfer means is a means for transferring the toner image on the photoreceptor to a transfer body (intermediate transfer body or transfer material). When an intermediate transfer body is used, the primary transfer roller becomes the transfer means. Since the "transfer means" in the present invention is a means for transferring the "toner image on the photoreceptor", the secondary transfer roller used when transferring from the intermediate transfer body to the transfer material is not included in the "transfer means".
[0294] 5 transfers the toner image formed on the photoconductor 111Y onto the endless belt-like intermediate transfer body 131. The primary transfer roller 133Y is disposed in contact with the intermediate transfer body 131.
[0295] In the image forming apparatus 100 shown in FIG. 5, an intermediate transfer method is adopted in which the toner images formed on the photoconductors 111Y, 111M, 111C, and 111Bk are transferred to the intermediate transfer body 131 by primary transfer rollers (primary transfer means) 133Y, 133M, 133C, and 133Bk, and each toner image transferred to the intermediate transfer body 131 is transferred to the transfer material P by a secondary transfer roller (secondary transfer means) 217, but a direct transfer method may also be adopted in which the toner images formed on the photoconductors are transferred directly to the transfer material P by a transfer means.
[0296] The transfer means according to the present invention is characterized in that a transfer bias having the same polarity as the toner particles is applied to the non-image area on the photoconductor. It is preferable that the transfer bias applied to the non-image area on the photoconductor has the same polarity as the toner particles and has an absolute value larger than the surface potential of the photoconductor.
[0297] This makes it difficult for toner particles applied to the non-image area on the photoconductor by a fog toner supplying mechanism described later to be transferred to the transfer body, and allows the toner particles to be efficiently supplied to the cleaning means.
[0298] <4.5 Cleaning Method> The cleaning means is a means for removing the toner particles remaining on the surface of the photoreceptor.
[0299] 8 is a schematic diagram showing the relationship between the cleaning blade and the photoconductor from the side. The cleaning means 119Y shown in FIG. L The cleaning blade C is made up of a support member Pg. L is disposed so that its tip faces in the opposite direction (counter direction) to the rotation direction of the photoconductor 111Y at a contact portion C with the surface of the photoconductor 111Y.
[0300] Cleaning blade C according to the present invention L is the edge angle θ of the tip ridge e It is preferable that the edge angle θ is in the range of 90 to 130 degrees. e This refers to the angle of the leading edge of the contact portion C with the surface of the photoconductor 111Y.
[0301] Edge angle θ e By making the wedge angle θ3 90° or more, the wedge angle θ3 becomes small, and a shearing action that cleaves and spreads the layered crystals of the lubricant is obtained, thereby improving the surface lubricity. L and the ridgeline on the upstream side in the rotation direction of the photoconductor 111Y.
[0302] Edge angle θ e By keeping the wedge angle θ3 at 130° or less, the abrasiveness is appropriate and lubrication is effectively obtained. In addition, the force with which the toner particles push the blade vertically upward is not too large, so cleaning failure is unlikely to occur.
[0303] In addition, the edge angle θ e When the angle is within the range of 90 to 130°, stick-slip vibration of the cleaning blade is reduced, and the slip-through of toner particles is improved, thereby improving cleaning performance.
[0304] Edge angle θ e From the viewpoint of effectively improving surface lubricity and cleaning properties, the angle is preferably 95° or more and 110° or less.
[0305] Cleaning blade C according to the present invention L It is preferable that the cleaning blade C is pressed against the surface of the photoconductor 111Y so that the effective contact angle θ1 is within a range of 7 to 20°. L and the ridgeline on the downstream side in the rotation direction of the photoconductor 111Y.
[0306] By making the effective contact angle θ1 7° or more, the wedge angle θ3 becomes small, and a shearing action that cleaves and spreads the layered crystals of the lubricant is obtained, thereby improving the surface lubricity.
[0307] By setting the effective contact angle θ1 to 20° or less, the wedge angle θ3 does not become too small, the abrasiveness becomes appropriate, and the lubrication is effectively obtained. In addition, the force with which the toner particles push the blade vertically upward is not too large, so that cleaning failure is unlikely to occur.
[0308] From the viewpoint of effectively improving the surface lubricity, the effective contact angle θ1 is preferably 9° or more and 17° or less.
[0309] Edge angle θ e and the effective contact angle θ1 is the cleaning blade C L The deflection can be calculated using the cross-sectional shape and physical properties such as Young's modulus of the material.
[0310] Cleaning Blade C LFrom the viewpoints of abrasion resistance and moldability, it is preferable that the polyurethane is used. Examples of polyurethane include those obtained by reacting a polyol, a polyisocyanate, and, if necessary, a crosslinking agent.
[0311] Cleaning Blade C L It may have a single layer structure, or may have a multi-layer structure in which a support layer and a contact layer are laminated.
[0312] Cleaning Blade C L The hardness of the cleaning blade C is preferably within the range of 65 to 85° as defined by JIS-A. L The wedge angle θ3 does not become too small. Also, if the hardness is 85° or less, the surface pressure does not become too large, the polishing force does not become too strong, and the lubricant is not easily removed, so that the lubricant effect is sufficiently obtained.
[0313] Cleaning Blade C L The rebound resilience is preferably within a range of 10 to 40°. If the rebound resilience is within the above range, vibration is appropriately suppressed, the wedge angle θ3 is stabilized, and the shearing action of the fatty acid metal salt can be more effectively exerted.
[0314] Cleaning Blade C L It is preferable that the free length L is within a range of 8.5 to 11.5 mm, and the thickness is within a range of 1.7 to 2.5 mm.
[0315] Cleaning Blade C L From the viewpoint of preventing incomplete wiping and curling, the contact force is preferably within the range of 12 to 30 (N / m). If the contact force is 12 (N / m) or more, there is no risk of incomplete wiping, and if it is 30 (N / m) or less, there is no risk of curling.
[0316] The support member Pg may be a conventionally known one, and examples of such a support member include those made of rigid metal, elastic metal, plastic, ceramic, etc. Among these, rigid metal is preferable.
[0317] <4.6 Lubricant supply means> The lubricant supplying means is a means for adhering a lubricant to the surface of the photoreceptor in order to supply the lubricant to the cleaning means.
[0318] In the image forming system of the present invention, a lubricant supplying means may be provided, but since toner particles containing a lubricant as an external additive are used, a lubricant can be supplied to the cleaning means even without a separate lubricant supplying means.
[0319] <5. Fog toner supply mechanism> In the present invention, the "fogging toner supply mechanism" refers to a mechanism that supplies toner particles to a cleaning means by applying the toner particles to a non-image area on a photoreceptor. The electrophotographic image forming system of the present invention is characterized by being provided with the fogging toner supply mechanism.
[0320] By supplying the toner particles to the cleaning means, the toner particles scrape off the lubricant from the part of the photoconductor where the amount of lubricant attached is large, and the amount of lubricant attached can be made uniform. This fogging toner is supplied to the cleaning means by being applied to the non-image area on the photoconductor. This makes it possible to supply the toner particles applied from the developing means to the cleaning means as fogging toner, for example, without providing a separate toner supply unit after the transfer means.
[0321] The amount of fogging toner supplied to the cleaning means is preferably about 1.8 mg per A4 sheet when images are continuously formed on the A4 sheet, for example.
[0322] The following two mechanisms can be used as the fogging toner supply mechanism. Mechanism A: Toner particles are applied to the non-image areas on the photoreceptor by making the fogging margin of the non-image areas on the photoreceptor different from the fogging margin of the image areas on said photoreceptor. Mechanism B: The toner particles are applied to the non-image areas on the photoreceptor by exposing the entire non-image areas to light using an exposure means.
[0323] The following describes the mechanism A and mechanism B. The fog toner supply mechanism according to the present invention is preferably mechanism A, since it can efficiently supply toner particles.
[0324] (Mechanism A) Mechanism A is a mechanism for applying toner particles to the non-image area on the photoreceptor by making the fogging margin of the non-image area on the photoreceptor different from the fogging margin of the image area on the photoreceptor.
[0325] The "fog margin" refers to the bias difference between the charging DC bias and the developing DC bias, and can be expressed by the following formula. Fog margin [V] = Charging DC bias [V] - Development DC bias [V]
[0326] The "charging DC bias" refers to a DC voltage applied to a charging member by a charging means to control the potential of the photoreceptor surface, and the "developing DC bias" refers to a DC voltage applied to a developer carrier when developing toner by a developing means.
[0327] In the case of a general device that does not apply toner particles to non-image areas on the photoreceptor, the positive and negative values of the fog margin are set to be the same as the positive and negative polarities of the toner particles in both image and non-image areas. This ensures that toner particles are not applied to non-image areas that are not exposed to light, and that toner particles are applied only to areas of the image area that have been exposed to light and have an electrostatic latent image potential.
[0328] In contrast, if the charging DC bias and the developing DC bias are adjusted so that the positive and negative values of the fog margin in the non-image areas are reversed to the positive and negative polarities of the toner particles, it is possible to apply toner particles to the non-image areas on the photoreceptor even when the photoreceptor is not exposed to light.
[0329] For example, when the polarity of the toner particles is negative, the charging DC bias is fixed at -500V, and the developing DC bias is set to -400V in the image area and -550V in the non-image area. As a result, the fog margin in the image area is -100V, and the positive and negative values of the fog margin and the positive and negative polarity of the toner particles are the same. On the other hand, the fog margin in the non-image area is +50V, and the positive and negative values of the fog margin and the positive and negative polarity of the toner particles are reversed. As a result, in the image area, the toner particles are applied only to the area that has become the electrostatic latent image potential due to exposure, but in the non-image area, the toner particles are applied to the photoconductor even without exposure.
[0330] (Mechanism B) Mechanism B is a mechanism for applying the toner particles to the non-image areas on the photoreceptor by exposing the non-image areas with an exposure means.
[0331] In the case of a general device that does not apply toner particles to non-image areas on a photoconductor, only the areas of the image area to which toner particles are applied are exposed to light to create an electrostatic latent image potential, but areas of the image area to which toner particles are not applied and non-image areas are not exposed to light. As a result, toner particles are not applied to the non-image areas that are not exposed, and toner particles are applied only to the areas of the image area that have become electrostatic latent image potential due to exposure.
[0332] On the other hand, when the entire non-image area is exposed by the exposure means, the toner particles can be applied to the non-image area as well. EXAMPLES
[0333] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified.
[0334] <1. Preparation of photoconductor> A photoreceptor was prepared using the following materials and procedures.
[0335] <1.1 Binder resin for photoconductor> Polycarbonate resin A (Iupizeta (registered trademark) FPC-0220 (polymer of bisphenol AP), viscosity average molecular weight: 20,000, manufactured by Mitsubishi Gas Chemical Company, Inc.) Polycarbonate resin B (same skeleton as Iupizeta (registered trademark) FPC-0220, viscosity average molecular weight: 40,000, manufactured by Mitsubishi Gas Chemical Company, Inc.) Polycarbonate resin C (same skeleton as Iupizeta (registered trademark) FPC-0220, viscosity average molecular weight: 50,000, manufactured by Mitsubishi Gas Chemical Company, Inc.) Polycarbonate resin D (copolymer of bisphenol AP and dihydroxy compound, viscosity average molecular weight: 30,000, manufactured by Mitsubishi Gas Chemical Co., Ltd.) Polycarbonate resin E (copolymer of bisphenol AP and dihydroxy compound, viscosity average molecular weight: 35,000, manufactured by Mitsubishi Gas Chemical Company, Inc.) Polycarbonate resin F (Iupizeta (registered trademark) FPC-6535A (copolymer of bisphenol Z and dihydroxy compound), viscosity average molecular weight: 33,000, manufactured by Mitsubishi Gas Chemical Company, Inc.) Polycarbonate resin G (Iupizeta (registered trademark) PCZ-300 (polymer of bisphenol Z), viscosity average molecular weight: 30,000, manufactured by Mitsubishi Gas Chemical Company, Inc.)
[0336] Resins A to E have a partial structure represented by the above general formula (1-1), and resins F and G have a partial structure represented by the above general formula (2).
[0337] <1.2 Inorganic particles for photoreceptors> Hydrophobic silica A (AEROSIL (registered trademark) RX300, number primary average particle size 7 nm, manufactured by Nippon Aerosil Co., Ltd.) Hydrophobic silica B (AEROSIL (registered trademark) NAX50, number primary average particle size 30 nm, manufactured by Nippon Aerosil Co., Ltd.) Hydrophobic silica C (AEROSIL (registered trademark) RX50, number primary average particle size 40 nm, manufactured by Nippon Aerosil Co., Ltd.) Hydrophobic silica D (AEROSIL (registered trademark) VP RX40S, number primary average particle size 90 nm, manufactured by Nippon Aerosil Co., Ltd.) Hydrophobic silica E (AEROSIL (registered trademark) SX110, number primary average particle size 110 nm, manufactured by Nippon Aerosil Co., Ltd.) Alumina (AEROSIL (registered trademark) RXC65K1, number primary average particle size 17 nm, manufactured by Nippon Aerosil Co., Ltd.)
[0338] <1.3 Preparation of photoreceptor 1> Photoreceptor 1 was prepared according to the following procedure.
[0339] (Conductive support) The surface of a cylindrical aluminum support having a diameter of 30 mm was machined to prepare a conductive support having a surface roughness Rz of 1.5 (μm).
[0340] (Middle class) The following materials were mixed and dispersed in a sand mill for 10 hours in a batch system. After leaving it to stand overnight, it was filtered (filter: Nippon Pall Corporation Rigimesh 5 μm filter was used) to prepare an intermediate layer coating solution. This coating solution was applied to the conductive support by dip coating to form an intermediate layer with a dry thickness of 2 μm.
[0341] Polyamide resin CM8000 (Toray Industries, Inc.) 1 part by weight Titanium oxide SMT500SAS (manufactured by Teika Co., Ltd.) 3 parts by weight Methanol 20 parts by weight
[0342] (Charge generation layer) The following materials were mixed and dispersed for 10 hours using a sand mill to prepare a charge generating layer coating solution. This coating solution was applied onto the above intermediate layer by dip coating to form a charge generating layer with a dry thickness of 0.3 μm. The titanyl phthalocyanine pigment below has a maximum diffraction peak at least at 27.3° in Cu-Kα characteristic X-ray diffraction spectrum measurement.
[0343] Charge generating material: titanyl phthalocyanine pigment 20 parts by weight Polyvinyl butyral resin 10 parts by mass t-Butyl acetate 700 parts by mass 4-Methoxy-4-methyl-2-pentanone 300 parts by mass
[0344] The polyvinyl butyral resin used was #6000-C manufactured by Denki Kagaku Kogyo Co., Ltd.
[0345] (charge transport layer) The following materials were mixed to prepare a charge transport layer coating solution. This coating solution was applied onto the charge generation layer by dip coating to form a charge transport layer with a dry thickness of 20 μm. The following polycarbonate resin F is a copolymer of bisphenol Z and a dihydroxy compound, and has a viscosity average molecular weight of 33,000.
[0346] Polycarbonate resin F 100 parts by mass Charge transport material: CTM-1 (chemical formula below) 50 parts by weight Antioxidant 2 parts by weight Tetrahydrofuran 540 parts by mass Toluene 135 parts by mass Silicone oil (KF-54: Shin-Etsu Chemical Co., Ltd.) 0.3 parts by weight
[0347] [ka]
[0348] The antioxidant used was Irganox 1010 manufactured by BASF Japan.
[0349] (protective layer) The following materials were mixed to prepare a solution. Next, 30 parts by mass of silica particles AEROSIL (registered trademark) RX50 (manufactured by Nippon Aerosil Co., Ltd., number primary average particle diameter 40 nm) surface-modified with hexamethyldisilazane as inorganic fine particles were ultrasonically dispersed in 400 parts by mass of tetrahydrofuran, and the dispersion was mixed with this solution to prepare a protective layer coating liquid. Then, this coating liquid was applied onto the charge transport layer using a circular slide hopper type coater, and dried at 120°C for 70 minutes to form a protective layer with a dry film thickness of 17 μm, and a photoreceptor 1 was obtained. The following polycarbonate resin A is a polymer of bisphenol AP, and has a viscosity average molecular weight of 20,000.
[0350] Polycarbonate resin A 50 parts by weight Polycarbonate resin F 50 parts by weight Charge transport material: 50 parts by weight of CTM-1 having the above chemical structure Antioxidant 2 parts by weight Tetrahydrofuran 400 parts by mass Toluene 200 parts by mass Silicone oil (KF-54: Shin-Etsu Chemical Co., Ltd.) 0.3 parts by weight
[0351] The antioxidant used was Irganox 1010 manufactured by BASF Japan.
[0352] <1.4 Preparation of photoreceptors 2 to 28> Photoreceptors 2 to 28 were prepared in the same manner as in the preparation of photoreceptor 1, except that the types and amounts of binder resin and inorganic fine particles added were changed as shown in the table below.
[0353] <1.5 Preparation of photoconductor 29> Photoreceptor 29 was prepared in the same manner as in the preparation of photoreceptor 1, except that the protective layer was not formed and the charge transport layer was formed as follows.
[0354] (charge transport layer) The following materials were mixed to prepare a solution. Next, 30 parts by mass of silica particles AEROSIL (registered trademark) RX50 (manufactured by Nippon Aerosil Co., Ltd., number-first average particle diameter 40 nm) surface-modified with hexamethyldisilazane as inorganic fine particles were ultrasonically dispersed in 400 parts by mass of tetrahydrofuran, and the dispersion was mixed with this solution to prepare a charge transport layer coating liquid. Then, this coating liquid was applied onto the charge generation layer by a dip coating method, and dried at 120°C for 70 minutes to form a charge transport layer with a dry thickness of 37 μm, and a photoreceptor 29 was obtained.
[0355] Polycarbonate resin C 50 parts by mass Polycarbonate resin F 50 parts by weight Charge transport material: 50 parts by weight of CTM-1 having the above chemical structure Antioxidant 2 parts by weight Tetrahydrofuran 80 parts by mass Toluene 120 parts by mass Silicone oil (KF-54: Shin-Etsu Chemical Co., Ltd.) 0.3 parts by weight
[0356] The antioxidant used was Irganox 1010 manufactured by BASF Japan.
[0357] <1.6 Preparation of photoreceptors 30 to 32> Photoreceptors 30 to 32 were prepared in the same manner as in the preparation of photoreceptor 29, except that the types and amounts of binder resin and inorganic fine particles added were changed as shown in the table below.
[0358] <2. Preparation of toner particles> Toner particles 1 to 16 were prepared according to the following procedure.
[0359] <2.1 Preparation of toner particles 1> The procedure for preparing toner particles 1 is as follows.
[0360] (Preparation of dispersion of resin particles for core part) A surfactant solution prepared by dissolving 4 parts by mass of sodium polyoxyethylene-2-dodecyl ether sulfate in 3,040 parts by mass of ion-exchanged water was charged into a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, and the internal temperature was raised to 80°C while stirring at a stirring speed of 230 rpm under a nitrogen stream.
[0361] To this surfactant solution, a polymerization initiator solution prepared by dissolving 10 parts by mass of a polymerization initiator (potassium persulfate: KPS) in 400 parts by mass of ion-exchanged water was added, and the temperature was raised to 75°C. After that, a monomer mixture consisting of 532 parts by mass of styrene, 200 parts by mass of n-butyl acrylate, 68 parts by mass of methacrylic acid, and 16.4 parts by mass of n-octyl mercaptan was added dropwise over one hour.
[0362] This system was heated and stirred at 75°C for 2 hours to carry out polymerization (first-stage polymerization), thereby preparing a dispersion of resin fine particles [A]. The weight-average molecular weight (Mw) of the resin fine particles [A] prepared in the first-stage polymerization was 16,500.
[0363] The weight average molecular weight (Mw) was measured using "HLC-8220" (manufactured by Tosoh Corporation) and a column "TSKguardcolumn + TSKgelSuperHZM-M triple column" (manufactured by Tosoh Corporation). While maintaining the column temperature at 40°C, tetrahydrofuran (THF) was passed as a carrier solvent at a flow rate of 0.2 ml / min. The measurement sample was dissolved in tetrahydrofuran to a concentration of 1 mg / ml under dissolution conditions in which the sample was treated for 5 minutes at room temperature using an ultrasonic disperser. The sample solution was then processed through a membrane filter with a pore size of 0.2 μm to obtain a sample solution. 10 μl of this sample solution was injected into the device together with the above carrier solvent and detected using a refractive index detector (RI detector). The molecular weight distribution of the measurement sample was calculated using a calibration curve measured using monodisperse polystyrene standard particles. As the standard polystyrene sample for the calibration curve measurement, a molecular weight of 6 × 10 2 , 2.1×10 3 , 4×10 3 , 1.75×10 4 , 5.1×10 4, 1.1×10 5 , 3.9×10 6 , 8.6×10 5 , 2×10 6 , 4.48×10 6 At least 10 standard polystyrene samples were measured and a calibration curve was created. A refractive index detector was used as the detector.
[0364] In a flask equipped with a stirrer, 93.8 parts by mass of paraffin wax "HNP-57" (manufactured by Nippon Seiro Co., Ltd.) was added as a release agent to a monomer mixture consisting of 101.1 parts by mass of styrene, 62.2 parts by mass of n-butyl acrylate, 12.3 parts by mass of methacrylic acid, and 1.75 parts by mass of n-octyl mercaptan, and the mixture was heated to 90°C to dissolve.
[0365] Meanwhile, a surfactant solution prepared by dissolving 3 parts by weight of sodium polyoxyethylene-2-dodecyl ether sulfate in 1,560 parts by weight of ion-exchanged water was heated to 98°C, and 32.8 parts by weight (solid content equivalent) of the dispersion of the resin microparticles [A] described above was added to this surfactant solution. The monomer solution containing the paraffin wax was mixed and dispersed for 8 hours using a mechanical disperser "Clearmix" (manufactured by M Technique Co., Ltd.) with a circulation path, to prepare a dispersion containing emulsified particles having a dispersed particle size of 340 nm.
[0366] Next, a polymerization initiator solution prepared by dissolving 6 parts by mass of potassium persulfate in 200 parts by mass of ion-exchanged water was added to the emulsion particle dispersion, and the system was heated and stirred at 98°C for 12 hours to carry out polymerization (second-stage polymerization), thereby preparing a dispersion of resin fine particles [B]. The weight-average molecular weight (Mw) of the resin fine particles [B] prepared in the second-stage polymerization was 23,000.
[0367] A polymerization initiator solution prepared by dissolving 5.45 parts by mass of potassium persulfate in 220 parts by mass of ion-exchanged water was added to the above resin particles [B], and a monomer mixture consisting of 293.8 parts by mass of styrene, 154.1 parts by mass of n-butyl acrylate, and 7.08 parts by mass of n-octyl mercaptan was added dropwise over one hour under a temperature condition of 80°C.
[0368] After the dropwise addition was completed, polymerization (third-stage polymerization) was carried out by heating and stirring for 2 hours, and then the mixture was cooled to 28°C to obtain a dispersion of core resin particles. The core resin particles had a weight-average molecular weight (Mw) of 26,800. The core resin particles had a volume-based average particle size of 125 nm. The core resin particles had a glass transition temperature (Tg) of 30.5°C.
[0369] (Preparation of dispersion of resin particles for shell layer) In the first step of the polymerization for preparing the dispersion of the core resin particles, the monomer mixture was changed to 548 parts by mass of styrene, 156 parts by mass of 2-ethylhexyl acrylate, 96 parts by mass of methacrylic acid, and 16.5 parts by mass of n-octyl mercaptan, but the polymerization reaction and post-reaction treatment were carried out in the same manner to prepare a dispersion of the shell resin particles. The glass transition temperature (Tg) of the shell resin particles was 49.8°C.
[0370] (Preparation of Colorant Microparticle Dispersion) 90 parts by mass of sodium dodecyl sulfate was added to 1,600 parts by mass of ion-exchanged water, and while stirring this solution, 420 parts by mass of carbon black "Regal 330R" (manufactured by Cabot Corporation) was gradually added. Next, a dispersion process was performed using a stirring device "Clearmix" (manufactured by M Technique Co., Ltd.) to prepare a colorant microparticle dispersion in which colorant microparticles are dispersed.
[0371] The particle size of the colorant particles in this colorant particle dispersion was measured using an electrophoretic light scattering photometer "ELS-800" (manufactured by Otsuka Electronics Co., Ltd.) and found to be 110 nm.
[0372] (Formation of the core) 420 parts by mass (solid content equivalent) of a dispersion of resin microparticles for the core part, 900 parts by mass of ion-exchanged water, and 100 parts by mass of a dispersion of colorant microparticles were placed in a reaction vessel equipped with a temperature sensor, a cooling tube, a nitrogen introducing device, and a stirring device, and stirred.
[0373] The temperature inside the reaction vessel was adjusted to 30° C., and then a 5 mol / L aqueous solution of sodium hydroxide was added to this solution to adjust the pH to 8-11.
[0374] Next, an aqueous solution of 60 parts by mass of magnesium chloride hexahydrate dissolved in 60 parts by mass of ion-exchanged water was added at 30°C over a period of 10 minutes while stirring. After leaving the mixture for 3 minutes, the temperature was raised to 80°C (core formation temperature) over a period of 80 minutes.
[0375] In this state, the particle size was measured using a flow particle image analyzer "FPIA2100" (manufactured by Sysmex Corporation). When the volume-based average particle size of the particles reached 5.8 μm, an aqueous solution of 40.2 parts by mass of sodium chloride dissolved in 1,000 parts by mass of ion-exchanged water was added to stop the particle size growth. Further, as a maturation treatment, the liquid was heated and stirred at a temperature of 80°C (core maturation temperature) for 1 hour to continue the fusion and form a core.
[0376] The circularity of the core was measured using a flow type particle image analyzer "FPIA2100" (manufactured by Sysmex Corporation) and was found to be 0.930.
[0377] In addition, the core portion was observed at 10,000 times magnification using a scanning transmission electron microscope (JSM-7401F, manufactured by JEOL Ltd.) to confirm that the colorant had dissolved in the binder resin and that no dispersed colorant particles remained.
[0378] (Shell layer formation) Next, 46.8 parts by mass (solid content equivalent) of a dispersion of resin particles for the shell layer was added at 65°C. Furthermore, an aqueous solution in which 2 parts by mass of magnesium chloride hexahydrate was dissolved in 60 parts by mass of ion-exchanged water was added over 10 minutes. Thereafter, the temperature was raised to 80°C (shell formation temperature) and stirring was continued for 1 hour to fuse the particles of the resin particles for the shell layer to the surface of the core part.
[0379] Then, the mixture was aged at 80°C (shell aging temperature) until it reached a predetermined circularity, forming a shell layer. An aqueous solution of 40.2 parts by mass of sodium chloride dissolved in 1000 parts by mass of ion-exchanged water was added, and the mixture was cooled to 30°C at a rate of 8°C / min. The fused particles thus formed were filtered and repeatedly washed with ion-exchanged water at 45°C. Then, the mixture was dried with hot air at 40°C.
[0380] By the above procedure, toner base particles having a shell layer on the core surface and negative polarity were obtained. The toner base particles had a volume-based average particle size of 5.9 μm, a glass transition temperature (Tg) of 31° C., and an average circularity of 0.960.
[0381] (Addition of external additives)
[0382] External additives were added to the toner base particles prepared as described above in the following procedure. Two types of fatty acid metal salt particles were added as lubricants. Hereinafter, of the two types of lubricants added in the production of each toner, the lubricant with the smaller volume-based average particle size will be referred to as "lubricant (1)" and the lubricant with the larger volume-based average particle size will be referred to as "lubricant (2)."
[0383] To 100 parts by mass of the dried toner base particles, 0.12 parts by mass of zinc stearate particles ("MZ-2" volume-based average particle size 2.0 μm; manufactured by NOF Corporation) were added as lubricant (1), and the mixture was mixed for 3 minutes using a Henschel mixer "FM10B" (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a stirring blade peripheral speed of 15 m / sec and a processing temperature of 30°C.
[0384] Next, 0.75 parts by mass of small-diameter silica fine particles ("RX-200" fumed silica HMDS-treated, number-average particle diameter 12 nm; manufactured by Nippon Aerosil Co., Ltd.), 1.50 parts by mass of spherical silica fine particles ("X-24 9600" sol-gel-processed silica HMDS-treated, number-average particle diameter 80 nm; manufactured by Shin-Etsu Chemical Co., Ltd.), 0.08 parts by mass of zinc stearate particles ("ZnSt-S"; manufactured by NOF Corp., adjusted to a volume-based average particle diameter of 10.0 μm) as a lubricant (2), and 0.5 parts by mass of calcium titanate particles ("TC110" number-average primary particle diameter 300 nm, silicone oil-treated, manufactured by Titan Kogyo Co., Ltd.) as metal oxide fine particles with high polishing effect were added, and the mixture was mixed for 15 minutes at a stirring blade peripheral speed of 40 m / s and a treatment temperature of 30°C using a Henschel mixer "FM10B" (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.).
[0385] Thereafter, coarse particles were removed using a sieve with 90 μm openings, thereby preparing toner particles 1.
[0386] <2.2 Preparation of toner particles 2 to 16> In the preparation of toner particle 1, the toner base particles, lubricant (1), lubricant (2), and the volume-based average particle size of the metal oxide fine particles were changed as shown in Table I to prepare toner particles 2 to 16.
[0387] In Table I, "Amount added [parts by mass]" is the amount added relative to 100 parts by mass of the toner base particles. Also, "ZnSt," "MgSt," and "LiSt" stand for "zinc stearate," "magnesium stearate," and "lithium stearate," respectively.
[0388] <2.3 Measurement of volumetric particle size distribution of lubricants> The volume-based particle size distribution of the lubricant in toner particles 1 to 16 was measured by the following procedure.
[0389] 5 g of toner particles and 50 ml of a 0.7% aqueous solution of sodium dodecylbenzenesulfonate were placed in a 100 ml beaker and dispersed by stirring at 300 rpm for 5 minutes using a magnetic stirrer "Model MS500D" (manufactured by Yamato Scientific).
[0390] After the dispersion, ultrasonic vibration was applied to the toner dispersion liquid for 10 minutes using an ultrasonic homogenizer "US-1200T" (manufactured by Nippon Seiki Seisakusho) at a frequency of 20 kHz, OUTPUT scale 3, and TUNING scale 6.
[0391] The toner dispersion was centrifuged under the following conditions using a centrifuge, Model H-900 (manufactured by Kokusan Co., Ltd.) to separate the toner. Rotor: PC-400 (radius 18.1 cm) Rotation speed: 1200 rpm (292 G) Time: 10 minutes
[0392] After centrifugation, 40 ml of the supernatant was collected using a pipette so as not to include the settled toner base particles.
[0393] The volumetric particle size of the particles contained in the collected supernatant was measured using a flow particle image analyzer "FPIA-2100" (Sysmex Corporation) in the measurement range of 0.6 to 400 μm, to determine the volumetric particle size distribution of the lubricant.
[0394] The volumetric particle size distribution of the lubricant in toner particles 1 to 13 had two peaks, one on the small particle side and one on the large particle side. The volumetric average particle size of the lubricant having a peak on the small particle side (the lubricant on the small particle side) and the volumetric average particle size of the lubricant having a peak on the large particle side (the lubricant on the large particle side) are as shown in Table I.
[0395] The volumetric particle size distribution of the lubricant in the toner particles 14 to 16 did not have two peaks on the small particle size side and the large particle size side.
[0396] In the remarks column of Table I, the toner particles according to the present invention are marked with an ◯, and the particles not according to the present invention are marked with an X.
[0397] <3 Image forming system> Image forming systems 1 to 58 were prepared by using the above-mentioned photoconductors 1 to 32 and toner particles 1 to 16 in the combinations shown in Tables II to IV below in a full-color multifunction printer "bizhub C650i" (manufactured by Konica Minolta) equipped with a contact-type charging means (charging roller) or a full-color multifunction printer "bizhub C754" (manufactured by Konica Minolta) equipped with a non-contact-type charging means (corona discharge).
[0398] The edge angles of the ridges of the cleaning blades in the respective image forming systems are as shown in the table below.
[0399] The fog toner supply mechanism employs mechanism A, which applies toner particles to the non-image area on the photoreceptor by making the fog margin of the non-image area on the photoreceptor different from the fog margin of the image area on the photoreceptor, and is applied to all but the image forming systems 52 and 53.
[0400] Regardless of whether or not the fog toner supply mechanism is applied, the bias conditions for the image area on the photoconductor are as follows.
[0401] (Bias conditions for image area) Charged AC bias: +1800V Charging DC bias: -500V Photoconductor surface potential: -500V Developing bias: -400V Coverage margin: -100V Transfer bias: +800V
[0402] When the fog toner supplying mechanism was not applied, the bias conditions for the non-image area were not changed from those for the image area, and only when the fog toner supplying mechanism was applied, the bias conditions were changed as follows.
[0403] (Bias conditions for non-image areas when a fogging toner supply mechanism is applied) Charged AC bias: +1800V Charging DC bias: -500V Photoconductor surface potential: -500V Developing bias: -550V Coverage margin: +50V Transfer bias: -800V
[0404] <4 Exam> The image forming systems 1 to 58 were subjected to the following durability test.
[0405] (Long-term printing test) In an environment with a temperature of 23°C and a humidity of 50%, a text image with an image ratio of 5% was continuously printed on 300,000 sheets of A4 paper in landscape orientation on both sides.
[0406] (Low temperature and low humidity test) After the long-term printing test, only the photoconductor of the image forming unit was removed from the image forming system and a new photoconductor was installed for evaluation. Using the new photoconductor, blank images with an image ratio of 0% were printed intermittently on one side of 5,000 sheets (7P / J) in landscape feed A4 format in an environment with a temperature of 10°C and a humidity of 20%. If the image could no longer be output before the number of printed sheets reached 300,000 in the long-term printing test, the test was moved to a low temperature and low humidity test at that point.
[0407] <5 Rating> After the durability test, the image forming systems 1 to 58 were evaluated for filming resistance and average wear, and the image forming systems 29 and 37 to 58 were further evaluated for the amount of lubricant attached, the wear gradient, and the occurrence of charging failure. The results of each evaluation are shown in the table below.
[0408] (Anti-filming) After the long-term printing test and the low-temperature, low-humidity test, the surface of the photoreceptor was visually observed and observed under an optical microscope at 100 magnifications for any deposits, and evaluated according to the following criteria.
[0409] ⊚: No deposits were observed under an optical microscope (100x). ◯: No adhesion was observed with the naked eye, but was observed under an optical microscope (100x). ×: Adherence was visually observed. In addition, if the length of the long side of the deposit is 200 μm or more, it is considered that it can be observed with the naked eye.
[0410] ◎ and ○ were evaluated as pass, and × was evaluated as fail. For image forming systems 24, 26, 27, 28, 32, and 36, the photoconductor became worn out and images could not be output before the number of printed sheets reached 300,000, so evaluation after the long-term printing test could not be performed.
[0411] (Average depletion amount) The average thickness of the outermost surface layer of the photoreceptor after the long-term printing test was measured, and the average wear amount [μm / 100krot] was calculated. The average thickness of the surface layer was measured at 10 random locations in the uniform area (excluding the leading and trailing ends where the thickness is likely to vary during coating) using an eddy current film thickness measuring device "EDDY560C" (manufactured by HELMUT FISCHER GMBTE CO.), and the average value was calculated. The difference in the average thickness of the outermost surface layer after the long-term printing test was taken as the average wear amount, and the average wear amount per 100krot (100,000 rotations) was calculated. The smaller the average wear amount, the better the wear resistance was evaluated. It is practically preferable that the average wear amount is 2.0μm / 100krot or less.
[0412] (Amount of lubricant attached) The amount of lubricant adhered to the photoreceptor after the long-term printing test [atm %] was measured using ESCA (Electron Spectroscopy for Chemical Analysis) at a position 5 cm from the end of the R side of the photoreceptor (upstream side in the direction of transport of the developer) and at a position 5 cm from the end of the F side of the photoreceptor (downstream side in the direction of transport of the developer).
[0413] (Depletion slope amount) The thickness of the outermost surface layer of the photoconductor after the long-term printing test was measured using an eddy current film thickness gauge "EDDY560C" (manufactured by HELMUT FISCHER GMBTE CO.) at a position 5 cm from the end of the R side of the photoconductor (upstream side in the direction of transport of the developer) and at a position 5 cm from the end of the F side of the photoconductor (downstream side in the direction of transport of the developer), and the difference between the measured values was taken as the wear slope amount [μm].
[0414] (Whether or not charging failure occurs) The occurrence of charging failure due to wear gradient in a long-term printing test was evaluated. Specifically, the occurrence of fogging due to charging failure occurs in the thick film portion when wear gradient occurs, so the occurrence of fogging was evaluated.
[0415] [Table 1]
[0416] [Table 2]
[0417] [Table 3]
[0418] [Table 4]
[0419] From the above examples, it is apparent that the electrophotographic forming system of the present invention has better evaluation results than the comparative example, and is able to achieve both wear resistance and filming resistance of the photoreceptor. [Explanation of symbols]
[0420] 11 Charging roller 11a Core metal 11b Elastic layer 11c Resistance Control Layer 11d surface layer 11e Compression spring 100 Image forming device 110Y, 110M, 110C, 110Bk Image forming unit 111Y, 111M, 111C, 111Bk photoconductor 113Y, 113M, 113C, 113Bk Charging means (charging roller) 115Y, 115M, 115C, 115Bk Exposure means 117Y, 117M, 117C, 117Bk developing means 118Y, 118M, 118C, 118Bk developing roller 119Y, 119M, 119C, 119Bk Cleaning means 133Y, 133M, 133C, 133Bk Transfer means (primary transfer roller) 301 Conductive Support 302 Photosensitive layer 303 Middle Class 304 Charge generation layer 305 Charge transport layer 306 Protective layer 310 Photoreceptor C L Cleaning blade P g Supporting member C Contact part θ1 effective contact angle θ2 Rigid body contact angle θ3 wedge angle θ e Edge Angle
Claims
1. 1. An electrophotographic imaging system for forming an image with toner particles, comprising: The image forming apparatus includes a photoconductor, a charging unit, an exposure unit, a developing unit, a transfer unit, and a cleaning unit, The photoreceptor is configured by laminating a photosensitive layer on a conductive support, the photosensitive layer has at least a charge generating layer and a charge transport layer, the outermost layer of the photosensitive layer contains a polycarbonate having a partial structure represented by the following general formula (1), inorganic fine particles, and a charge transport material, the toner particles contain toner base particles and an external additive, The external additive is at least a lubricant, the volumetric average particle size distribution of the lubricant has two peaks, one on the small particle size side and the other on the large particle size side, the volumetric average particle size of the lubricant having the peak on the small particle size side is 3.0 μm or less, and the volumetric average particle size of the lubricant having the peak on the large particle size side is larger than the volumetric average particle size of the toner base particles, A fog toner supply mechanism is provided for supplying the toner particles to the cleaning means by applying the toner particles to a non-image area on the photoreceptor.
23. An electrophotographic imaging system comprising: 【Chemistry 1】 (In the formula, R 1 and R 2 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group; R 1 Or R 2 At least one of R represents a phenyl group. 3 ~R 10 each independently represents a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms.
2. The photosensitive layer has a protective layer as the outermost layer.
2. An electrophotographic imaging system according to claim 1.
3. The outermost layer of the photosensitive layer further contains a polycarbonate having a partial structure represented by the following general formula (2):
3. An electrophotographic imaging system according to claim 1 or 2. 【Chemistry 2】
4. The number average primary particle size of the inorganic fine particles is within a range of 5 to 100 nm.
4. An electrophotographic imaging system according to claim 1.
5. The inorganic fine particles are hydrophobic silica.
5. An electrophotographic imaging system according to claim 1.
6. The volume-based average particle size of the lubricant having a peak on the small particle size side is within a range of 1.0 to 3.0 μm, and the volume-based average particle size of the lubricant having a peak on the large particle size side is within a range of 8.0 to 15.0 μm.
6. An electrophotographic imaging system according to claim 1.
7. The lubricant is at least one of zinc stearate particles, lithium stearate particles, and magnesium stearate particles.
7. An electrophotographic imaging system according to claim 1.
8. The fog toner supply mechanism applies the toner particles to the non-image area on the photoconductor by making a fog margin of the non-image area on the photoconductor different from a fog margin of the image area on the photoconductor.
8. An electrophotographic imaging system according to claim 1.
9. The transfer means applies a transfer bias having the same polarity as that of the toner particles to a non-image area on the photoreceptor.
9. An electrophotographic imaging system according to claim 1.
10. The cleaning means includes a cleaning blade that is pressed against the surface of the photoreceptor so that the edge angle of the tip edge portion is within a range of 90 to 130 degrees.
10. An electrophotographic imaging system according to claim 1.
11. The charging means is of a contact type.
11. An electrophotographic imaging system according to any one of claims 1 to 10.
Citation Information
Patent Citations
Organic photoreceptor, image forming method, image forming apparatus and process cartridge
JP2003316036A
Electrophotographic photoreceptor and device and process cartridge using the same
JP2003316038A
Organic photoreceptor, process cartridge, and image forming apparatus
JP2006301247A
Cleaning device for image forming apparatus, process cartridge and image forming apparatus
JP2010156778A
Image forming apparatus and method for controlling sticking of lubricant to image carrier
JP2011007831A